Identification of novel loci regulating circulating melatonin and its causal relationship with hypertension - Lin Yan; Yang Qiu; Zhiwen Mo; Mingli Li; Xueran Huang; Yongfen Gao; Boteng Yan; Qiantu Hu; Haiying Zhang; Zengnan Mo; Rui Lin (Human Genetics, 2026)

Integrative multi-omics analysis and machine learning identify M2 macrophage–induced ferroptosis resistance in glioblastoma - Fangzhou Guo; Teng Deng; Jun Yan; Yong Mo; Qianrong Huang; Qian Jiang; Ligen Mo; Shipeng Ning; Chao Li (Functional & Integrative Genomics, 2026)

Controls of marine isoprene distributions in the western Arctic Ocean - Miming Zhang; Dennis Booge; Keyhong Park; Shibo Yan; Jinyoung Jung; Youngju Lee; Ahra Mo; Qian Shi; Yanfang Wu; Chunyang Li (Marine Environmental Research, 2026)

Targeted emission controls for ozone pollution mitigation based on mesoscale weather pattern classifications in China’s Pearl River Delta region - Aoxing Zhang; Jiongkai Chen; Huiran Feng; Wei Tao; Jiajia Mo; Wenlu Wu; Jianfeng Guo; Tianle Sun; Long Yun; Min Yan; Xiaolin Wang; Tzung-May Fu (ENGINEERING Environment, 2026)

A general near-infrared fluorescence analysis platform via N-substituent modulation of tricyclic boronic ester hemicyanine dyes - Ruyu Yan; Yuetian Li; Zhenming Hao; Keke Yao; You Zhou; Liming Hu; Shanyan Mo (Analytica Chimica Acta, 2026)

Tailoring imidazolium-based deep eutectic solvents via hydrogen bond donor regulation for efficient extraction of polycyclic aromatic hydrocarbons - Kaihao Mo; Peng Cui; Cailan Chen; Hanyu Zhang; Yan Huang; Peiwen Wu; Haiyan Ji; Wenshuai Zhu (Journal of Environmental Chemical Engineering, 2026)

Study on emulsification property of chitosan with strong antibacterial activity - Junqing Qian; Junlan Yin; Peilong Ma; Chenghong Mo; Yan Chen; Hui Guo (Food Hydrocolloids, 2026)

Arabinose enables anti-corrosion and uniform Sn deposition for ultrastable Sn-MnO2 aqueous batteries - Yan Xu; Xueyao Mo; Jinchi Li; Ming Song; Xuena Xu; Liluo Shi; Yidong Miao; Wenyi Tan; Dongliang Chao; Wanhai Zhou (Chemical Engineering Journal, 2026)

Autocatalytic DNA nanosphere assembly activated by endogenous APE1 for intracellular miR-21 imaging - Liuting Mo; Chunfen Zhang; Rongzheng Yuan; Yan Hong; Chan Yang; Weiying Lin (Analytica Chimica Acta, 2026)

Rapid Detection of Spring Viremia of Carp Virus ( SVCV ) Using RAA ‐ CRISPR /Cas12a - Xiaoyang Li; Aoqing Zhang; Yingying Li; Yingying Wang; Hao Zheng; Defeng Zhang; Yan Ren; Xubing Mo; Yuting Deng; Junyu Luo; Meiling Yu; Bo Chen; et al. (Journal of Fish Diseases, 2026)
Spring viremia of carp virus (SVCV), that can infect cyprinoid and koi causing an acute hemorrhagic symptom, with a feature of widespread epidemic, which poses a severe threat to the global aquaculture industry. Given the absence of specific effective medicine or vaccines, the early, accurate diagnosis is critical in the disease prevention. Many SVCV detection methods have been established, but most require specialized equipment and skilled operators, which limits their field application. In this study, we established a recombinase‐mediated isothermal amplification (RAA) in conjunction with the CRISPR/Cas12a system targeting the screened conserved region of the G gene in the genome to identify SVCV. The optimal combination of the primer pairs and crRNA was screened via the fluorescence intensity. In addition, the test exhibited high sensitivity and specificity, which could detect at the limit of 1.243 × 10 1 copies/μL and show no cross‐reactivity with other common freshwater fish pathogens. Furthermore, the result could be visible by excitation of fluorophores by blue light at 39°C within 30 min. The integrated method combines the advantages of RAA and CRISPR‐based signal transduction, offering a diagnosis project in resource‐limited aquaculture environments and a field‐applicable early warning of SVCV.

Study on the behavioral and metabolic response mechanisms of Peronia verruculata to marine heatwaves - Rui Gao; Xiaolong Gao; Maninder Meenu; Mo Zhang; Xinyu Yan; Ying Liu (Marine Pollution Bulletin, 2026)

Associations of salinity and microplastics with microbial community assembly and functional potential in saline-alkali soils - Caidan Ding; Wen Hu; Xiuyuan Yang; Guanhai Mo; Linfeng He; Qiuxiao Yan; Zhenming Zhang (Journal of Hazardous Materials, 2026)

Inhibition of protein-bound heterocyclic amines by citrus polymethoxyflavones via stabilizing myofibrillar protein conformation - Hui Xin; Diaodiao Yang; Shigang Liu; Lan Mo; Lei Zhou; Aihua Lou; Yan Liu; Qingwu Shen; Maomao Zeng; Jie Chen; Chaoyi Xue; Wei Quan; et al. (Food Chemistry, 2026)

Microeukaryotes are more vulnerable than picoeukaryotes to reservoir salinization: Evidence from multi-year high-frequency monitoring - Wanting Shi; Yuanyuan Mo; Hongteng Zhang; Erik Jeppesen; Xue Yan; Huihuang Chen; Haihan Zhang; Jun Yang (Environmental Research, 2026)

DSTs may affect the swimming ability of marine medaka by interfering with the neurotransmitter system and calcium signaling - Zi-min Chen; Mei-qi Li; Jing-xuan Jiang; Yan-hang Mo; Da-wei Li; Hong-ye Li; Wei-dong Yang (Environmental Pollution, 2026)

Taihu Lake Region Geosites: Preliminary Geoheritage Inventory in a Historically Developed and Geologically Rich Area of SE China - Weilun Kong; Yunhuai Li; Kongliang Li; Degao Wang; Fangxu Wang; Mo Chen; Lijun Chen; Yan Peng; Yujuan Liu; Chenchen Zhan; Jifei Hu (Geoheritage, 2026)

Effect of phosphate concentration on resistance of Pyropia yezoensis (Bangiales, Rhodophyta) to red rot disease (Pythium porphyrae) - Congcong Sun; Huichao Yang; Yongwei Yan; Zhaolan Mo; Yunxiang Mao; Jie Li (Journal of Applied Phycology, 2026)

Strigolactones restrict sugar acquisition in rice tiller buds to inhibit their outgrowth through suppressing the expression and polarized localization of two monosaccharide transporters - Tianhao Wang; Tianyu Mo; Yinglu Sun; Miao Miao; Yan Chun; Ashmit Kumar; Jinfeng Zhao; Xueyong Li (Molecular Plant, 2026)

Synergistic depression of chalcopyrite by Fe(II) and Na2S in Chalcopyrite-Molybdenite separation: Mechanism investgation and industrial validation - Zhian Liang; Langfeng Tang; Zhenpeng Han; Tao Yue; Songtao Yang; Qiankun Wang; Zhenjun Mo; Haixiang Wu; Zhuanhua Wei; Yan Miao; Luzheng Chen (Minerals Engineering, 2026)

Development of an innovative in-situ solid-state fermentation system based on endophytic fungi and agrifood by-products pigeon pea roots to enhance genistein production - Jin-Xian Fu; Mo-Nan Wen; Jiao Jiao; Qing-Yan Gai; Yu-Jie Fu; Dan Qu (Innovative Food Science & Emerging Technologies, 2026)

MeHg bioaccumulation and n-3/n-6 PUFA profiles in fish from karst rice–fish co-culture systems: Dietary health trade-offs - Min Jing; Ting Dai; Sisi Mo; Xiaolong Wang; Haiyu Yan (Environmental Pollution, 2026)

Multi-omics analysis of LFA-1 peptide-functionalized silk fibroin nanofibers targeting RPE and activating AMPK–HO-1 signaling to suppress pyroptosis and alleviate diabetic retinopathy progression - Zepeng Xu; Chenxiao Lu; Zhenting Wang; Yaojia Liu; Guangmeng Mo; Yan Yang; Xiaoli Lu; Kunmeng Li; Yihuan Zeng; Yan Dong; Ni Tian (Chemical Engineering Journal, 2026)

Biomass-assisted water electrolysis with liquid antimony anode for high efficiency hydrogen evolution - Xin Gu; Mei Zhou; Yidong Jiang; Yuting Li; Chaojun Liu; Jiongyuan Huang; Wenfei Mo; Xiaoyi Liu; Huihuang Fang; Wei Yan; Kongfa Chen; Yixiang Shi; et al. (Chemical Engineering Journal, 2026)

Synthesis of NiFe-Fc-MOF/LDH/NF with tip effect enhancing electric field for oxygen evolution reactions - Xiangyu Meng; Liang Ma; Zengyan Wei; Jia Song; Fengqi Zhang; Shihao Wu; Mo Yan; Bo Chen; Lin Zhu; Dechang Jia; Yu Zhou; Xiaoming Duan (Chemical Engineering Journal, 2026)

Effects of norgestrel on the reproductive endocrine system, hepatic damage and antioxidant responses of marine medaka (Oryzias melastigma) at different salinities - Jian Song; Chao Zheng; Yan-Qiu Liang; Zhongdian Dong; Chang-Gui Pan; Wen-Jun Shi; Qidan Zheng; Shuhui Zhou; Mingwei He; Xipeng Mo; Zhong Lin (Aquatic Toxicology, 2026)

Unveiling Key Factors in Determining Biodegradable Mulching Film Adoption Through Evolutionary Game Analysis - Wanying Lin; Xi Mo; Luca Nizzetto; Xuan Shi; Yuan Chen; Jinhui Li; Yan Lin (Bulletin of Environmental Contamination and Toxicology, 2026)

Functional noncoding variants within the TBX1 enhancer contribute to tetralogy of Fallot - Jimiao Gao; Tao Jiang; Yingyi Quan; Xinyue Liu; Min Da; Jiang Jiang; Jun Zhou; Hao Sun; Yan Zhou; Wanting Ma; Zicheng Zhang; Yiwei Cheng; et al. (Science China Life Sciences, 2026)

A radial velocity estimation method of the underwater moving target based on vector sound field - Bo Wang; Shiqi Mo; Xingyu Huang; Xueyi Yan (Ocean Engineering, 2026)

Bioremediation of α-terpineol-contaminated flotation wastewater using biochar-immobilized biosurfactant-producing bacteria - Jin-Cheng Ye; Ying-Xi Liu; Huan Du; You-Qun Xie; Lei Xiang; Bai-Lin Liu; Nai-Xian Feng; Yan-Wen Li; Quan-Ying Cai; Ce-Hui Mo; Hai-Ming Zhao (Journal of Environmental Management, 2026)

Molten salt − assisted graded carbonization tailors hard carbon pores toward enhanced sodium ions storage - Zuqin Duan; Rui Tang; Ying Mo; Peng Gao; Yan Duan; Hui Liu; Aiping Hu; Jilei Liu (Fuel, 2026)

Vpa1463, a DUF1566-domain protein, is indispensable for bile resistance and biofilm formation in Vibrio parahaemolyticus and is required for its adaptation to food-related environments - Min Chu; Jingli Li; Yu Sun; Xuehu Liu; Qiufen Mo; Yanming Ren; Yan Wang; Menghua Yang; Guangzhi Xu; Qinxue Ni (Food Research International, 2026)

Sweet liker status moderates the relationship between perceived stress and snack preference - Jessica C. McCormack; Kean Yung Wong; Ai Ting Goh; Elizabeth Agbor Epse Muluh; Maggie Hames; Stephanie C. McLeod; Yunfan Mo; Yuqing Yan; Mei Peng (Food Quality and Preference, 2026)

Enhancing Daily Runoff Prediction Accuracy with the Coupled KAN-LSTM Model and a Dynamic Postprocessing Module - Chongxun Mo; Tao Feng; Keke Huang; Zhiwei Yan; Zihan Lin; Haiyang Wang; Jiameng Xu; Yuyi Zhong; Gang Tang; Yi Huang (Water Resources Management, 2026)

RNA regulation in plants - Yijun Qi; Yueqin Chen; Hongwei Guo; Huishan Guo; Runlai Hang; Guifang Jia; Yan Li; Beixin Mo; Zhen Wang; Liang Wu; Yiji Xia; Xiaofei Yang; et al. (Science China Life Sciences, 2026)

Identification of Metabolism-Related Genes with Potential Diagnostic Value in Gestational Diabetes Mellitus - Yan Mo; Yan-Yuan Bai; Xiu-Fang Li; Hua Zhang; Juan Liang; Wen-Juan Zhang; Li Lu; Wan-tao Liang (Indian Journal of Clinical Biochemistry, 2026)

High-density lipoprotein antioxidant function is associated with lipid profiles and lipid-lowering therapy - Hong-Yu Cao; Zhi-Wei Mo; Zhen-Sheng Ma; Yi-Fang Liu; Chen Wang; Yue-Ming Peng; Yue-Ting Kang; Yan Li; Zhi-Jun Ou; Jing-Song Ou (Science China Life Sciences, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

PhysTrack: Physics-driven multi-AUV tracking from UAV imagery via pose estimation and dynamic state inference - Jifeng Zhu; Wenyu Cai; Meiyan Zhang; Wen Wu; Yan Ma; Yuchang Mo (Ocean Engineering, 2026)

A novel PGPR Streptomyces sp. for efficient phthalate biodegradation: Mechanistic insights and application in contaminated soil - Hong-Jia Huang; Yi-Tong Huang; Miao Xin; Xiao-Qiong Zhu; Hui LYU; Jiayu Hu; Lei Xiang; Yan-Wen Li; Hai-Ming Zhao; Quan-Ying Cai; Meng Li; Da-Wei Li; et al. (Journal of Hazardous Materials, 2026)

Efficient production of high-performance thermally conductive adhesives by in situ one-pot liquid-phase exfoliation approach - Tonghao Zhu; Sha Wang; Chen Chen; Jiaying Mo; Huijian Ye; Weili Yan; Yufei Li; Mingxing An; Lixin Xu (Chemical Engineering Journal, 2026)

Bone transport accelerates diabetic foot ulcer healing via TGF-β1–mediated angiogenic and osteo-immune coupling - Yan Chen; Xiajie Huang; Chaoquan Yang; Xiaomei Wu; Ying Li; Yingrong Liao; Xinyun Liang; Yangzhou Mo; Caiyun Xie; Yicheng Liang; Haidong Chen; William Lu (Journal of Molecular Histology, 2026)

Multi-objective two-stage optimization of canal system scheduling in irrigation districts incorporating groundwater dynamic variations - Huiying Zhou; Tianxiao Li; Qiang Fu; Mo Li; Tienan Li; Yan Liu (Agricultural Systems, 2026)

Single-cell and spatial transcriptomics identify PGK1-sensitized hypoxia macrophages as a therapeutic target to overcome PDT resistance in glioma - Xiuwei Yan; Jiahe Hu; Xuyan Han; Lei Xu; Lihui Zhou; Jiaoyan He; Fei Yang; Longgang Zhou; Yapeng Niu; Mo Geng; Wenjie Yuan; Dong Zhao; et al. (Journal of Photochemistry and Photobiology B: Biology, 2026)

Multifunctional bacterial consortium degrading phthalates, promoting plant growth and inhibiting soil-borne pathogenic fungi - Jie-bin Zhou; Qiong-Wen Zhang; Yong-Ling Zhou; Hai-Feng Chen; Yu-Hong Huang; Hai-Ming Zhao; Lei Xiang; Yan-Wen Li; Ce-Hui Mo; Quan-Ying Cai; Qing X. Li (Journal of Hazardous Materials, 2026)

Evaluation of gamma irradiation on the microbiological, phytochemicals, and aromatic profiles of sun-bleached preserved pepper (Capsicum annuum L.) - Mengyun Ouyang; Sheng Cao; Yiji Zhou; Mo Mo; Yuanfang Xu; Qiling Zhang; Yong Zhang; Chao Deng; Feng Guo; Hui Song; Yan Wang; Yiqun Huang; et al. (Food Chemistry, 2026)

An interpretable ensemble machine learning model for predicting carbon dioxide adsorption on magnesium oxide-based sorbents - Lin Fan; Yan He; Yunfeng Mo; Yiming Cao (Environmental Research, 2026)

Cell-specific gene expression plasticity in response to hypoxia promotes high-altitude adaptive evolution - Wen-Tian Wei; Ze Yan; Hui Wu; Ming-Liang Zhou; Dong-Xin Mo; Xing Wan; Rui Ma; Mei-Ming Wu; Jia-Hui Huang; Ya-Jing Liu; Ji Yang; Meng-Hua Li (Science China Life Sciences, 2026)

Upregulation of m6A writer WTAP by histone lactylation promotes inflammatory response via TLR2 in neutrophils - Bailu Du; Wenting Song; Yiming Zhang; Yan Yin; Yuanjie Zhou; Yi Pan; Ruwen Yang; Muxiu Jiang; Nan Shen; Qihua Fu; Jianye Zang; Yue Tao; et al. (Science China Life Sciences, 2026)

In vitro and ex vivo Pharmacological Profile of HY-022619, a Novel Intravenous P2Y12 Receptor Antagonist with Rapid-onset and Sustained Antiplatelet Activity - Jiajia Mo; Emily M. He; Yan Zhao; Li Shao; Shaoyun Yue; Yanmei Xie; Shiqi Wu; Jianxun He; Yi Zou; Zhaoxing Chu; Guangwei He; Yungen Xu (Pharmaceutical Research, 2026)

Identifying Salt-tolerant Andrographis paniculata Germplasms: A Comparative Study - Yan-hua Shao; Ye Liu; Xun-lang Jian; Shi-lun Mo; Quan Yang; Ming Li (Journal of Plant Growth Regulation, 2026)

Sorption and degradation of α-terpineol in soils with distinct physicochemical properties - Huan-Feng Chen; Zi-Jun Yang; Hai-Rong Chen; Hai-Ming Zhao; Yan-Wen Li; Quan-Ying Cai; Ce-Hui Mo; Lei Xiang (Environmental Geochemistry and Health, 2026)

BGR-net: A boundary-guided refinement network for multi-class cloud detection - Shaowei Bai; Yan Mo; Wanting Zhou (Remote Sensing Applications: Society and Environment, 2026)

Silkworm excrement–immobilized bacteria for synergistic remediation of phthalate esters in agricultural soil - Yong-Hong Chen; Huan Du; Ying-Xi Liu; Ke Xu; Jin-Cheng Ye; Bai-Lin Liu; Nai-Xian Feng; Lei Xiang; Yan-Wen Li; Quan-Ying Cai; Ce-Hui Mo; Hai-Ming Zhao (Journal of Hazardous Materials, 2026)

Integrative analysis reveals casing layer dynamics during Agaricus bisporus cultivation and the growth promoting effect of Pseudomonas putida AT130 - Hongtu Li; Zunjie Xi; Huayu Zhong; Xiaoming Yan; Tongtong Mo; Qin Chen; Dongdong Mu; Xuefeng Wu; Xingjiang Li (Food Bioscience, 2026)

Bioactive biphasic textile scaffold for spatiotemporal regulation of inflammation and osteogenesis in enthesis healing during anterior cruciate ligament reconstruction - Meilin Song; Yanran Du; Haohan Li; Jiankun Feng; Xianchao Li; Yakun Huang; Yu-Qing Zhao; Chengbo Li; Huanhuan Yan; Dongsheng Li; Xiumei Mo; Guige Hou; et al. (Chemical Engineering Journal, 2026)

Reconstructing all-weather remotely sensed air temperature via a kernel-based temporal filling and bias correction (KTF-BC) framework - Yan Xin; Yongming Xu; Xudong Tong; Meng Ji; Yaping Mo; Yonghong Liu; Shanyou Zhu (Remote Sensing of Environment, 2026)

A CPTu-based method for evaluating consolidation characteristics of under-consolidated soils - Yu-cheng Li; Pin-Qiang Mo; Guojun Cai; Zhao Lu; Yan Zhuang; Hai-Sui Yu (Ocean Engineering, 2026)

Joint optimization of prediction and control under data-limited conditions: Enhanced modeling of wastewater treatment processes based on the TEASG optimization framework - Jian Chen; Zhicheng Deng; Jinquan Wan; Yan Wang; Suhua Yu; Wanqiu Mo (Journal of Water Process Engineering, 2026)

Effective separation of organic species from a shale oil sludge - He-Qi Liu; Xian-Yong Wei; Zhi-Hao Ma; Jing Chen; Xiao-Yan He; Zhi-Min Zong; Xing Fan; Yu-Hong Kang; Fang-Jing Liu; Hai-Xu Zou; Guang-Hui Liu; Yierxiati Dilixiati; et al. (Journal of Environmental Management, 2026)

Enhancing climate resilience of global dryland maize to cope with future 50-year climate warming - Jing Wang; Bao-Zhong Wang; Fei Mo; Yinglong Chen; Mohammad Ashraf; Yang Wang; Jian-Ming Li; Hai-Xia Duan; Yajie Song; Levis Kavagi; Hong-Yan Tao; You-Cai Xiong (Global Environmental Change, 2026)

Coral mucus input promotes sedimentary organic matter degradation: Evidence from a typical coral reef area, northern South China Sea - Bo Yang; Bin Yang; Lei Xie; Zhenjun Kang; Xiaorong Mo; Qin Li; Jiaodi Zhou; Haifang Huang; Tingting Yan; Cheng Xu (Environmental Research, 2026)

A near-infrared ratiometric fluorescent probe for visual sensing of H2S and monitoring its fluctuation in plant roots under drought and flooding stresses - Ruxuan Mo; Chao Kang; Jianping Yuan; Carl Redshaw; Ying Huang; Qilong Zhang; Xiufang Yan (Analytica Chimica Acta, 2026)

Long-term study shows cyanobacterial blooms reduce ciliate functional stability by altering network complexity - Mamun Abdullah Al; Zijie Xu; Jun Zuo; Peng Xiao; Yuanyuan Xue; Shuzhen Li; Xue Yan; Yuanyuan Mo; Qingyun Yan; Henglong Xu; Markus Majaneva; Erik Jeppesen; et al. (Algal Research, 2026)

Linking microbial life history strategy to carbon use efficiency under changing substrate and nutrient conditions - Gang Huang; Yan-feng Cao; Meng-hui Dong; Mo Bahram; Yan-gui Su (CATENA, 2026)

A novel pathologic scoring system for predicting postoperative recurrence in BCLC stage 0-A hepatocellular carcinoma patients: a nationwide multicenter study - Feng Xia; Jing Yan; Xulin Liu; Zhao Huang; Zhancheng Qiu; Qiao Zhang; Zhenheng Wu; Zhiyuan Huang; Renjie Wei; Li Lin; Liping Liu; Shuangqin Han; et al. (Science China Life Sciences, 2026)

Coordinated yet allometric leaf-root biogeochemical niche dynamics underlies divergent growth predictability under N addition - Xian-Meng Shi; An-Xin Liu; Yu-Xuan Mo; Sujan Balami; Jin-Hua Qi; Yang Liu; Zi-Yan Chen; Liang Song (Plant and Soil, 2026)

Probiotic Bacillus tequilensis protected Micropterus salmoides against Aeromonas veronii infection by modulating digestion, immunity, and intestinal microbiota and metabolites - Jianqiang Huang; Jingran Sun; Ling Pan; Fuping Song; Huiqin Huang; Kunlian Mo; Yan Wang; Yonghua Hu (Aquaculture, 2026)

Overlooked role of singlet oxygen in electrochemical processes for efficient sludge dewatering at neutral pH - Jialin Liang; Yu Zhang; Liang Zhang; Xiao Xiao; Zhihua Mo; Yan Zhou (Water Research, 2026)

Structural reconstruction-induced electronic Kagome lattices with low-energy flat bands in twisted double bilayer graphene - Mo-Han Zhang; Yalei Zhang; Chen-Yue Hao; Zi-Han Guo; Chao Yan; Ya-Xin Zhao; Ya-Ning Ren; Jin-Hua Gao; Shengjun Yuan; Lin He (Science Bulletin, 2026)

ROS responsive polydopamine coated black phosphorus nanocarrier for enhanced methylprednisolone delivery in acute lung injury immunotherapy - Zhiwei Gao; Mengxue Mo; Qianyue Liu; Jiaxiao Li; Hongshuai Zheng; Yaohui Huang; Yan Liu; Jing Qian; Xuzhi Liang; Yuting Xiao; Yan Long; Chen Qian; et al. (Chemical Engineering Journal, 2026)

Salvianolic Acid B Inhibits Ferroptosis Through ACSL4 Pathway Regulation in sepsis-associated encephalopathy Mice - Xingyao Li; Zhizhun Mo; Yumei Yang; Chunxia Zhao; Shuwen Zhang; Yan Lin; Yuxiang Liu; Ling Wang; Xiaolong Xu; Qingquan Liu; Kai Fan (Molecular Neurobiology, 2026)

Editorial Expression of Concern: Minocycline Protects Against NLRP3 Inflammasome-Induced Inflammation and P53-Associated Apoptosis in Early Brain Injury After Subarachnoid Hemorrhage - Jianru Li; Jingsen Chen; Hangbo Mo; Jingyin Chen; Cong Qian; Feng Yan; Chi Gu; Qiang Hu; Lin Wang; Gao Chen (Molecular Neurobiology, 2026)

17-Methoxyl-7-hydroxy-benzene-furanchalcone improves mitochondrial biogenesis and oxidative stress following myocardial ischemia/reperfusion injury through the AMPK/SIRT1 pathway based on network pharmacology - Yuanheng Huang; Yan Zhou; Qiuhua Qin; Sirui Mo; Zudong Xu; Zhiwei Tang; Yaosheng Wu; Feizhang Qin (Toxicology and Applied Pharmacology, 2025)

Complete loss of 5-methyltetrahydrofolate in wheat during simulated gastric digestion - Fengyuan Liu; Jinxian Zheng; Yunfei Mo; Yaping Xiao; Yun Wang; Hua Zhang; Jing-Kun Yan; Yaqing Liu (Food Chemistry, 2025)

Hydrological connection restoration may contribute more than species selection to organic carbon stock accumulation in mangrove - Qijuan Cao; Yuting Yang; Yan Lin; Lingling Zhong; Yutong Jin; Yujia Tian; Yuxi Chen; Luojian Mo; Yisheng Peng (Estuarine, Coastal and Shelf Science, 2025)

Structural characterization and oxidative stress modulation activity of an acidic Heteropolysaccharide from Microctis folium - Xiao-lu Liang; Yu-wen Liang; Jing Tian; Fei-fan Mo; Tian-ming Pan; Yan-feng Chen; Xiao-qi Shao; Kun-Ping Li (Carbohydrate Polymers, 2025)

Dynamics-Based Monitoring and Warning Systems for Rock Collapse Hazards: A Review and Field Implementations - Chen Chen; Mo-Wen Xie; Yan Du; Shuang-quan Li (Geotechnical and Geological Engineering, 2025)

PFKP Lactylation Promotes the Ovarian Cancer Progression Through Targeting PTEN - Jianfeng Mi; Ling Zhao; Yonglong Shen; Shien Mo; Yan Kuang (Biochemical Genetics, 2025)

Vasicine derivatives as potent MAPK inhibitors for psoriasis treatment - Qing-Yan Mo; Wen-Gang Wang; Xiao-Hong Li; Yun-Hong Shen; Yun Sun; Ze-Wei Mao; Chun-Ping Wan (Molecular Diversity, 2025)

Exploration of new azole derivatives containing ethanolamine moiety as anti-UC agents by inhibiting NF-κB/MAPK pathways - Ming-Qian Ju; Zheng-Xiao Huang; Qing-Yan Mo; Shuai Liu; Dong-Xue Wang; Yan-Ping Li; Chun-Ping Wan; Ze-Wei Mao (Molecular Diversity, 2025)

Enhanced bioremediation of α-terpineol-contaminated mining soil through immobilization of Indigenous biosurfactant-producing bacteria on biochar - Jin-Cheng Ye; Wei-Liang Li; You-Qun Xie; Huan Du; Lei Xiang; Bai-Lin Liu; Nai-Xian Feng; Yan-Wen Li; Quan-Ying Cai; Miaoyue Zhang; Ce-Hui Mo; Hai-Ming Zhao (Biology and Fertility of Soils, 2025)

Overlooked synergisms of flotation organic reagents and toxic metals in water: Formation of tridentate cadmium-xanthate complexes - Lei Xiang; Qian-Wen Wang; Wen-Jun Wu; Nian-Jue Zheng; Bai-Lin Liu; Yan-Wen Li; Quan-Ying Cai; Hai-Ming Zhao; Ce-Hui Mo; Qing X. Li (Water Research, 2025)

Caulerpin suppresses tumor-associated angiogenesis and tumor growth via Hippo signaling in cervical cancer - Guang Yang; Yan Mo; Honghong Rong; Bihui Guo; Qingbing Zha; Hanli Shuai; Minghua Wang; Ping Li (Toxicology and Applied Pharmacology, 2025)

The RLI1–OsPUB77–OsBZR3 module mediates the crosstalk between phosphate starvation and brassinosteroid signaling pathways to shape rice shoot architecture - Kai Wang; Peng Yan; Jiangfan Guo; Wei Li; Shichen Zhou; Yijian Liu; Jiming Xu; Yu Liu; Yunrong Wu; Zhongchang Wu; Peng Wang; Chuanzao Mao; et al. (Molecular Plant, 2025)

Origin of granitic pegmatites: Perspectives from elements and Li Hf isotopes, Chakabeishan, northern Tibetan Plateau - Wenli Sun; Zhidan Zhao; Xuanxue Mo; Guochen Dong; Xiaowei Li; Wanming Yuan; Tao Wang; Bingzhang Wang; Tong Pan; Jie Han; Yan Tang; Ningyuan Qi; et al. (Lithos, 2025)

Downscaling multilayer soil moisture using parameterized depth profiles associated with environmental factors - Mo Zhang; Yong Ge; Yuxin Ma; Yan Jin; Yingying Chen; Shaomin Liu (Journal of Hydrology, 2025)

Vibrio parahaemolyticus outer membrane porin Vpa0810 regulates its biofilm formation and plays a vital role in its stresses tolerance - Yu Sun; Min Chu; Chenzhi Zhuhuang; Yan Wang; Qiufen Mo; Qinxue Ni; Youzuo Zhang; Menghua Yang; Guangzhi Xu (International Journal of Food Microbiology, 2025)

Comparative study on the structural, antioxidant and functional properties of hydrolysates from Pleurotus erynigii and Pleurotus ostreatus protein by alcalase and trypsin - Xiao-Xuan Hou; Shu-Jing Bing; Man Hao; Jie Yang; Gui-Jin Sun; Ying-Qiu Li; Chen-Ying Wang; Yan Liang; Hai-Zhen Mo (Food Bioscience, 2025)

Complement factor D of Paralichthys olivaceus in serum enhances C3 deposition to activate complement against bacterial infection - Heng Liu; Xiao-yan Jin; Xue-pin Han; Yin Liu; Feng Zhang; Mo-fei Li (Fish & Shellfish Immunology, 2025)

Exploring the potential of UAV-based thermal imagery for monitoring diurnal variations in the microscale urban thermal environment - Meng Ji; Yongming Xu; Shanyou Zhu; Yang Zhang; Yan Xin; Yaping Mo (Energy and Buildings, 2025)

Dual-strategy stabilization of zinc anodes through solvation regulation and interfacial engineering in aqueous zinc ion batteries - Weilin Yan; Yifan Wang; Lufan Liu; Feiyu Tao; Yang Huang; Zhaoqian Li; Li'e Mo; Hong Zhang; Linhua Hu (Chemical Engineering Journal, 2025)

Gradient cellulose-based separator with dual nano-confinement and ion-guiding functions for dendrite-free zinc-ion batteries - Zhichao Liu; Qifan Liu; Haodao Mo; Yunyang Duan; Jisi Zhang; Zhenghu Sun; Yanfei Zeng; Dongliang Yan (Chemical Engineering Journal, 2025)

Effects of stringent industrial control during the Beijing Winter Olympics on bacterial variations in the atmosphere and built environments - Zhuo Chen; Fanxuan Xia; Yan Wang; Wuwei Zou; Jiyi Mi; Zhiwei Li; Tao Yu; Wenjun Leng; Jinhan Mo (Building and Environment, 2025)

Evapotranspiration Spatiotemporal evolution and its driving factors contribution analysis by SGC model of improved complementary correlation principle in Guangxi, China - Yunchuan Yang; Jiaqi Yao; Weiquan Wang; Liping Liao; Zongheng Li; Tao Yan; Yuxuan Zhou; Chongxun Mo; Xungui Li; Guikai Sun (Theoretical and Applied Climatology, 2025)

Metabolic Control of Stem Cell Function: Insights into Amino Acid-Driven Mechanisms - Jiawei Zeng; Xiaohao Liu; Jiaming Bi; Chuzi Mo; Han Zhang; Yan Chai; Yunhe Lin; Siwei Li; Zhongjun Liu; Mingyan Yao; Shuaimei Xu; Peiyan Yuan (Stem Cell Reviews and Reports, 2025)

Detection and automatic identification of landslide areas from the LiDAR point clouds using improved DBSCAN - Jiaqian Ma; Bin Luo; Yan Zhao; Shanwei Li; Mo Chen; Jian Wei; Shigang Wang; Xinyu Zhang (Landslides, 2025)

Optimizing soybean production and emission reduction through biogas slurry substitution and straw incorporation: A five-year field study in northeast China's black soil region - Pingan Zhang; Aizheng Yang; Xiaofang Wang; Lihong Wang; Yan Sha; Mo Li (Agriculture, Ecosystems & Environment, 2025)

Study on the role and function of RRS1 in cutaneous squamous cell carcinoma - Zhan-Yan Pan; Zhi-Nan Shi; Qiong Wu; Ting-Ting Hu; Xiao-Hui Mo; Da-Ke Dong; Qiang Ju (Tissue and Cell, 2025)

Title: Flue gas desulfurization gypsum amelioration affects the saline alkali soil microbial community on the temporal scale - Bangyan Liu; Shujuan Wang; Jia Liu; Yan Li; Lizhen Xu; Zhentao Sun; Enbo Mo; Yonggan Zhao (Soil and Tillage Research, 2025)

Interpretable machine learning models for predicting hormesis of binary antibiotic mixtures on Vibrio qinghaiensis sp.-Q67 - Ling-Yun Mo; Si-Tong Long; Pei-Pei Zhang; Yan-Peng Liang; Hong-Hu Zeng; Yong-Hong Zhang; Li-Tang Qin (Journal of Hazardous Materials, 2025)

Simplified synthetic community reveals the enrichment of phthalate-degrading bacteria in maize rhizosphere enhancing phthalate degradation - Jia-Lu Wei; Yu-Hong Huang; Jun-Hua Li; Huixiong Lü; Hai-Ming Zhao; Lei Xiang; Hui Li; Yan-Wen Li; Ce-Hui Mo; Quan-Ying Cai; Qing X. Li (Journal of Environmental Chemical Engineering, 2025)

Regulating the gel structure and digestive function of myofibrillar protein: The distinct roles of pre-hydrated curdlan and β-glucan - Shuai Jiang; Rongyu Yan; Fan Mo; Qian Liu; Ling Jiang (Food Chemistry, 2025)

Microemulsion-assisted synthesis of Mn-TCPP@MnxOy heterostructures for enhanced photodynamic therapy via O2 self-production and GSH-activatable imaging - Chan Yang; Yanling Zhao; Yanru Qin; Zihan Yan; Ziyi He; Nan Yang; Liuting Mo; Weiying Lin (Chemical Engineering Journal, 2025)

Corrigendum to “Engineered zwitterionic hydrogel with extreme environment resilience: High ionic conductivity, subzero tolerance, and potential for multimodal sensing and optical applications across devices” [Chem. Eng. J. 510 (2025) 161390/CEJ 161390] - Yan-Na Lu; Kai Mo; Mingwei Gu; Jia-Sen Xie; Ying Yang; Lin Zheng; Xiang-Ru Liu; Yunjie Lu; Jun-Shuai Chen; Jin Ge (Chemical Engineering Journal, 2025)

Unveiling the secret of cellular metamorphosis: the crucial role of EndMT mechanisms in COVID-19-induced pulmonary fibrosis - Xin Zhang; Xia Tong; Ruijie Hou; Pengbo Wang; Yan Mo; Lanlan Zhang (Inflammopharmacology, 2025)

High co-infection burden and ICU-specific pathogen profiles in pediatric Candida albicans respiratory infections: a large-scale tNGS analysis - Ya Huang; Huideng Zhou; Jiangyang Zhao; Lishai Mo; Junming Lu; Guangbing Liu; Shuo Zhang; Yanhua Feng; Wenting Tang; Qiang Huang; Yan Chen; Cuihong Lu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Regional variations in vegetation greening and climate change impacts on gross primary productivity and evapotranspiration in the Loess Plateau - Fen Gou; Wei Liang; Bojie Fu; Ning Chen; Weibin Zhang; Zhao Jin; Jianwu Yan; Yihe Lv; Xingguo Mo; Nan Gao (Agricultural and Forest Meteorology, 2025)

Identification and Analysis of Potential Biomarkers Associated with Neutrophil Extracellular Traps in Cervicitis - Wantao Liang; Yanyuan Bai; Hua Zhang; Yan Mo; Xiufang Li; Junming Huang; Yangliu Lei; Fangping Gao; Mengmeng Dong; Shan Li; Juan Liang (Biochemical Genetics, 2025)

Perfluorooctane sulfonate (PFOS) promotes transformational transfer of antibiotic resistance genes and cross-resistance between antibiotics and PFOS - Hui Zhao; Hai-Ming Zhao; Feng Wu; Bai-Lin Liu; Hui Li; Yan-Wen Li; Quan-Ying Cai; Lei Xiang; Ce Hui Mo; Qing X. Li (Water Research, 2025)

Sporopollenin-chitosan microspheres loaded with an endophytic fungus Talaromyces neorugulosus R-209 for promoting development and controlling root rot in pigeon pea - Jin-Xian Fu; Jiao Jiao; Qing-Yan Gai; Yu-Jie Fu; Mo-Nan Wen; Xiao-Qing Wang; Jing He (Journal of Plant Physiology, 2025)

Synergistic inhibition of Maillard reaction hazards: Multifunctional hydrocolloids enable healthier air-fried beef patties with reduced heterocyclic amines and AGEs - Hongfei Du; Huang Zhang; Zixin Zhang; Zihan Yuan; Maiquan Li; Lei Zhou; Yan Liu; Aihua Lou; Mei Li; Ye Jiao; Qingwu Shen; Chaoyi Xue; et al. (Food Chemistry, 2025)

Role of circular RNAs in formaldehyde-induced lung Injury: Insights into expression and regulatory pathways - Pan Ge; Xiang Zhang; Yan-qi Yang; Jia-ming Xie; Mo-qi Lv; Ying Sun; Ya-zhao Li; Yuan-yuan Geng; Jian Zhang; Dang-xia Zhou (Food and Chemical Toxicology, 2025)

Metallothioneins protect against isoconazole nitrate-induced antitumor activity through the maintenance of cellular redox homeostasis in hepatocellular carcinoma - Chun-fen Mo; Ya-ruo Lei; Jun Lin; Yi Liu; Zhi-wei Zhao; Wen-jing Xiao; Wen-bai Yan; Wei-wei Zhang (Chemico-Biological Interactions, 2025)

Plant morphological and physiological traits are stable in a nitrogen-saturated tropical forest after 18-year nitrogen additions - Guangcan Yu; Jing Chen; Andi Li; Senhao Wang; Liang Song; Xianmeng Shi; Junhua Yan; Meichen Xu; Yuewei Xue; Xiankai Lu; Wei Zhang; Juan Huang; et al. (Plant and Soil, 2025)

Preliminary Inventory and Assessment of the Geological Heritage of the Origin of Chinese Lingbi Stone - Weilun Kong; Yunhuai Li; Kongliang Li; Jun Chen; Degao Wang; Mo Chen; Yan Peng; Lijun Chen; Linghong Ge; Huiju Wu; Jifei Hu (Geoheritage, 2025)

Sustainable remediation of butyl xanthate-contaminated mine wastewater by combining emergent macrophyte Cyperus alternifolius with a versatile bacterial isolate - Qi Liu; Yao-Yao Ye; Sha Yang; Cheng-Yu Cui; Huan Du; Jin-Cheng Ye; Ji-Liang Cheng; Rui-Wen Hu; Lei Xiang; Bai-Lin Liu; Yan-Wen Li; Quan-Ying Cai; et al. (Journal of Hazardous Materials, 2025)

Efficiencies, pathways and mechanism on simultaneous biodegradation of phthalates and polycyclic aromatic hydrocarbons by bacterial consortium - Yao-Si Chen; Jia-Lu Wei; Jie-Bin Zhou; Yu-Hong Huang; Guang-Xuan Tang; Yan-Wen Li; Hai-Ming Zhao; Lei Xiang; Nai-Xian Feng; Ce-Hui Mo; Quan-Ying Cai; Qing X. Li (Journal of Environmental Chemical Engineering, 2025)

Corrigendum to “Synergistic effects of polymethoxyflavonoids from citrus peel extracts on harmful compound formation and flavor quality in grilled beef patties” [Food Chemistry 481 (2025) 1–11 144089] - Zhuoming Huang; Yang Xu; Ming Jin; Zixin Jiang; Lan Mo; Maiquan Li; Aihua Lou; Yan Liu; Chaoyi Xue; Jie Luo; Qingwu Shen; Shuai Wang; et al. (Food Chemistry, 2025)

Degradation efficiency for phthalates and cooperative mechanism in synthetic bacterial consortium and its bioaugmentation for soil remediation - Huixiong Lü; Yu-Hong Huang; Qi-Fang Li; Hai-Ming Zhao; Lei Xiang; Hui Li; Yan-Wen Li; Ce-Hui Mo; Quan-Ying Cai (Environmental Pollution, 2025)

In silico-guided engineering of broad-spectrum aptamer for the highly sensitive detection of organophosphate pesticides - Yalin Mo; Kuaile Wu; Yan Zheng; Ning Ma; Zhouping Wang; Shijia Wu; Nuo Duan (Chemical Engineering Journal, 2025)

Purification and characterization of cellulase produced by Bacillus sp. HMM - Lanqian Huang; Lei Mo; Jiaming Jiang; Yu Huo; Shisong Yu; Jianmei Ou; Siyu Liu; Xinyu Xie; Guyu Yan; Chuzun Liao; Shangxin Wu; Huiqing Zhang; et al. (Antonie van Leeuwenhoek, 2025)

Influence of oceanic emission and gas transfer velocity on atmospheric dimethyl sulfide distribution over the Southern Ocean - Jaemin Ju; Ahra Mo; Keyhong Park; Miming Zhang; Jinpei Yan; Jinyoung Jung; Louisa Emmons; Joo-Hong Kim; Taewook Park; Jisoo Park (Marine Pollution Bulletin, 2025)

Deciphering the complex roles of leucine-rich repeat receptor kinases (LRR-RKs) in plant signal transduction - Ting Tang; Ferdinand Ndikuryayo; Xue-Yan Gong; Elaheh Amirinezhadfard; Mehtab Muhammad Aslam; Mo-Xian Chen; Wen-Chao Yang (Plant Science, 2025)

Anti-sulfur poisoning and highly sensitive portable detection instrument for monitoring of hydrogen sulfide on-site - Wenjing Wang; Shenghong Li; Liumo Jiang; Xiaoju Cui; Yan Gao; Haijing Ning; Qinglian Li; Xiaolin Jiang; Mo Zhang; Dehui Deng; Yang Shu; Jianhua Wang; et al. (Journal of Hazardous Materials, 2025)

New insights into rhizosphere bacterial community shaped by lettuce genotypes for divergent degradation efficiencies of phthalates - Guang-Xuan Tang; Yu-Hong Huang; Li-Wan Feng; Yu-Chang Hu; Jia-Lu Wei; Huixiong Lü; Li-Hui Liu; Hai-Ming Zhao; Lei Xiang; Hui Li; Ce-Hui Mo; Yan-Wen Li; et al. (Journal of Hazardous Materials, 2025)

The tolerance mechanism of diarrhetic shellfish toxins mediated by the extracellular regulated protein kinase (ERK) pathway in the mussel Perna viridis - Jin-jin Lv; Yu-jie Liu; Yan-hang Mo; Li-yan Deng; Yang Liu; Hong-ye Li; Li Zhang; Wei-dong Yang (Journal of Hazardous Materials, 2025)

Synergistic effects of polymethoxyflavonoids from citrus peel extracts on harmful compound formation and flavor quality in grilled beef patties - Zhuoming Huang; Yang Xu; Ming Jin; Zixin Jiang; Lan Mo; Maiquan Li; Aihua Lou; Yan Liu; Chaoyi Xue; Jie Luo; Qingwu Shen; Shuai Wang; et al. (Food Chemistry, 2025)

Nickel foam-based preconcentrator for sensitive and accurate detection of low-concentration volatile organic compounds - Yan Wang; Dongqing Pang; Jinhan Mo; Zhuo Chen (Building and Environment, 2025)

A new method for mechanical identification of unstable sliding rock - Yan Du; Hong-da Zhang; Mo-wen Xie; Yu-jing Jiang; Santos Daniel Chicas; Jing-nan Liu (Bulletin of Engineering Geology and the Environment, 2025)

Modulation of the pyrolysis of ZIF-67 by kaolinite for highly efficient peroxymonosulfate activation - Yan Mo; Weiwei Yin; Chenhui Long; Chao Gao; Qihang Zhao (Applied Clay Science, 2025)

Pp07886, a glycoside hydrolase family 5 protein from Pythium porphyrae, is a required virulence factor and induces host disease resistance - Huichao Yang; Zhaolan Mo; Peiwen Weng; Yongwei Yan; Lei Tang; Xiaojun Rong; Jie Li (Algal Research, 2025)

Landform basis for the rise of early cities in the upper Jialu river basin, central China - Ye Li; Peng Lu; Panpan Chen; Hui Wang; Shugang Yang; Xiangli Zhao; Yinan Liao; Yan Tian; Zhen Wang; Duowen Mo (Quaternary International, 2025)

Three new polyketide metabolites from the endophytic fungus Trichoderma protrudens of Hibiscus tiliaceus - Yan-Mei Wu; Jing-Ya Mo; Yong-Yan Mei; Quan Liu; Yuan-Yuan Huang; Bei Zhou; Yi-Hang Li; Yan-Chun Wu; Jing-Quan Yuan (Phytochemistry Letters, 2025)

Uptake, translocation, and biotransformation of phthalate acid esters in crop plants: A comprehensive review - Nai-Xian Feng; Bogui Pan; Hong-Jia Huang; Yi-Tong Huang; Hui Lyu; Lei Xiang; Hai-Ming Zhao; Bai-Lin Liu; Yan-Wen Li; Quan-Ying Cai; Da-Wei Li; Ce-Hui Mo (Journal of Hazardous Materials, 2025)

Effects of novel bio-organic fertilizer on the remediation of PAEs-contaminated soil and its bacterial community composition - Hong-Jia Huang; Bogui Pan; Qi-Feng Liang; Wan-Ting Zhang; Yan-Wen Li; Lei Xiang; Hai-Ming Zhao; Bai-Lin Liu; Quan-Ying Cai; Nai-Xian Feng; Ce-Hui Mo (Journal of Environmental Chemical Engineering, 2025)

Growth promotion of synthetic microbial communities influenced by the function, diversity and interactions of their constituent strains and soil types - Bekzhan D. Kossalbayev; Mo Wei; Jingjing Wang; Yan Pang; Mingda Lv; Asemgul K. Sadvakasova; Meruyert O. Bauenova; Xiaoxia Zhang; Wei Zhao; Song Xu; Zhiyong Huang (World Journal of Microbiology and Biotechnology, 2025)

Deciphering the contribution of algae-rich microbial communities to dissolved organic matter in a eutrophic lake with distinct rainy and dry seasons - Han Yan; Hong-Fa Guo; Jia-Xun Li; Zhuo Chen; Shi-Qi Yin; Mo-Yu Shen; Yi Tao; Yin-Hu Wu; Hong-Ying Hu (Algal Research, 2025)

Inhibition of SIRT1/HSF1 pathway contributes to doxorubicin-induced nephrotoxicity in ovarian tumor-bearing mice - Mo Chen; Ying Zhao; Song Hu; Jun-bo Yuan; Kang-jie Xie; Shu-nv Cai; Xiao-yan Zhu; Jian-kui Du; Ping-bo Xu (Apoptosis, 2025)

2-Dodecyl-6-Methoxycyclohexa-2,5-Diene-1,4-Dione from Averrhoa carambola L. roots: Suppressing hepatocellular carcinoma progression through ROS accumulation and p53 pathway-mediated apoptosis - Meifeng Chen; Hongbing Pang; Thi Thai Hoa Pham; Yongfei He; Qiang Gao; Yuan Liao; Chunyi Zhu; Linqian Chen; Guohong Yan; Shutian Mo; Chuangye Han (Toxicology and Applied Pharmacology, 2025)

Highly tough and responsible ionic liquid/polyvinyl alcohol-based hydrogels for stretchable electronics - Pengcheng Zhou; Fan Mo; Zichong Ji; Jiawei Yang; Hongzhong Du; Zonglei Wang; Hossam Haick; Yan Wang (Science Bulletin, 2025)

Recovery and in-situ utilization of calcined petroleum coke from flotation spent carbon anodes - Zewen Mo; Xuewei Li; Xueyi Zhao; Jun Zhou; Xiaoqing Li; Wei Liu; Zhen Yao; Feiya Yan; Qifan Zhong (Journal of Environmental Management, 2025)

Cereal-legume intercropping stimulates straw decomposition and promotes soil organic carbon stability - Wei Wang; Meng-Ying Li; Qing-Hui Wen; Yue Ma; Zhi-Ming Zhang; Muhammad Maqsood Ur Rehman; Fei Mo; Hong-Yan Tao; Bao-Luo Ma; Joann K. Whalen; You-Cai Xiong (Science China Life Sciences, 2025)

Co-culture of Cajanus cajan (Linn.) Millsp. cell suspension cultures with an endophytic fungus for the enhanced production of pharmacologically active cajaninstilbene acid - Jin-Xian Fu; Jiao Jiao; Qing-Yan Gai; Yu-Jie Fu; Xiao-Qing Wang; Mo-Nan Wen; Jing He (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Tuning multi-scale pore structures in carbonaceous films via direct ink writing and sacrificial templates for efficient indoor formaldehyde removal - Zhuo Chen; Qiwei Chen; Yan Wang; Wuwei Zou; Yuan Li; Jinhan Mo (Journal of Hazardous Materials, 2025)

The inventory of OH and H2O in the non-polar regions of the Moon - Wen Yu; Hao Yan; Hong Tang; Xiongyao Li; Yu Wei; Huiming Bao; Chuanjiao Zhou; Bing Mo; Yanxue Wu; Haiyang Luo; Jialong Hao; Ruiying Li; et al. (Earth and Planetary Science Letters, 2025)

Engineered zwitterionic hydrogel with extreme environment resilience: High ionic conductivity, subzero tolerance, and potential for multimodal sensing and optical applications across devices - Yan-Na Lu; Kai Mo; Mingwei Gu; Jia-Sen Xie; Ying Yang; Lin Zheng; Xiang-Ru Liu; Yunjie Lu; Jun-Shuai Chen; Jin Ge (Chemical Engineering Journal, 2025)

Alzheimer’s Disease-Derived Outer Membrane Vesicles Exacerbate Cognitive Dysfunction, Modulate the Gut Microbiome, and Increase Neuroinflammation and Amyloid-β Production - Shouchao Wei; Xiaochen Ma; Yating Chen; Junjun Wang; Li Hu; Zhou Liu; Lang Mo; Ning Zhou; Wenrong Chen; He Zhu; Shian Yan (Molecular Neurobiology, 2025)

Discovery of novel benzbromarone derivatives via the closed metabolic site as potent human uric acid transporter 1 (URAT1) inhibitors - Wenfeng Ye; Mingchao He; Gaofeng Lin; Li Shao; Jiajia Mo; Yan Zhao; Xiaodong Ma; Qinlong Xu; Zhaoxing Chu (Medicinal Chemistry Research, 2025)

Molecular characterization of a novel mycovirus from Curvularia lunata in China - Bin Ke; Xiaohan Mo; Mengting Wu; Lin Wang; Ru Peng; Yuwen Lu; Jiejun Peng; Shaofei Rao; Guanwei Wu; Jianping Chen; Fei Yan; Hongying Zheng (Archives of Virology, 2025)

Development and Characterisation of an Immortal Cell Line From Largemouth Bass ( Micropterus salmoides ) for Viral Studies - Qianyi Mai; Qing Wang; Yingying Li; Jiyuan Yin; Xubing Mo; Cunbin Shi; Yan Ren; Donghai Liu; Xuanming Liu; Dongli Sun; Weiqiang Liu; Yuqi Jin; et al. (Journal of Fish Diseases, 2025)
Largemouth bass ( Micropterus salmoides ), a freshwater fish species, is cultivated widely across China. The industry has been greatly affected by various viral diseases. We generated a new immortal cell line from the fin of M. salmoides (MSF). It has been successfully maintained in continuous culture for over 80 passages. Cells multiply well at 28°C using Medium 199 or Leibovitz's L‐15 supplemented with 10%–20% fetal bovine serum. MSF cells comprise a mass of epithelialoid cells. Chromosome analysis showed that ploidy at passage 55 was 2 n = 58. Amplification and analysis of the sequence of cytochrome oxidase I gene ascertained the origin of MSF cells from M. salmoides . The cell line is devoid of contamination with mycoplasma. Successful transfection with a GFP reporter gene indicated that the MSF cell line can be a useful tool for further gene expression studies. MSF cells exhibited susceptibility to Largemouth bass ranavirus (LMBV), Infectious spleen and kidney necrosis virus (ISKNV), and Siniperca chuatsi rhabdovirus (SCRV). Transmission electron microscopy (TEM), and immunofluorescence confirmed that the MSF cell line showed high susceptibility to all the tested viruses. The titre values of MSF after infection with LMBV, ISKNV, and SCRV reached 10 7.4 TCID 50 /mL, 10 6.15 TCID 50 /mL, and 10 6.35 TCID 50 /mL at 7dpi, respectively. In conclusion, an immortal cell line derived from the fin tissue of M. salmoides was successfully developed and certain fish viruses can effectively propagated in the newly established MSF cell line that can be helpful for future gene manipulation and infectious viral mechanistic studies in the future.

Spatio-temporal ecological assessment of Camellia oleifera plantations using Sentinel-2 images based on deep learning - Yao Chen; Enping Yan; Shuyi Cao; Kaiqi Li; Dengkui Mo (International Journal of Remote Sensing, 2025)

Biochar strategy for long-term N2O emission reduction: Insights into soil physical structure and microbial interaction - Yeye Zhang; Chun Yan; Tao Wang; Guangxin Zhang; Michael Bahn; Fei Mo; Juan Han (Soil Biology and Biochemistry, 2025)

Microbial augmented aerobic composting for effective phthalates degradation in activated sludge - Bogui Pan; Hong Tian; Qi-Feng Liang; Hong-Jia Huang; Yi-Tong Huang; Bai-Lin Liu; Yan-Wen Li; Lei Xiang; Hai-Ming Zhao; Quan-Ying Cai; Nai-Xian Feng; Ce-Hui Mo (Journal of Environmental Management, 2025)

Extreme climate weakens the effect of biochar in increasing yield and reducing N2O emissions - Yeye Zhang; Ruixue Chen; Liru Yao; Chun Yan; Hongxia Li; Guangxin Zhang; Michael Bahn; Fei Mo; Juan Han (Field Crops Research, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Efficient extraction of Spirulina phycocyanin using natural deep eutectic solvents and its characteristics - Juying Lin; Jiaming Jiang; Lei Mo; Yu Huo; Yan Pang; Bingfeng Zhou; Changhua Shang (Algal Research, 2025)

Methyltransferase HsdM Regulates the Pathogenicity of Streptococcus agalactiae to Nile Tilapia (Oreochromis niloticus) - Dongdong Jiang; Bei Wang; Yan Ren; Xubing Mo; Meiling Yu; Defeng Zhang (Fishes, 2025)
DNA methylation is a critical mechanism for regulating gene expression in bacteria and plays an essential role in bacterial pathogenesis. A mutant, WC1535ΔhsdM, lacking hsdM encoding a DNA methyltransferase was constructed using homologous recombination technology. The growth, hemolytic activity, and capsule formation of the mutant were analyzed. The dynamic distribution of the wild-type (WT) and mutant strains in tilapia tissues after artificial infection was determined. The adhesion, invasion, anti-phagocytic, and whole-blood survival abilities of the WT and mutant strains were analyzed. Tilapia were intraperitoneally injected with the WT or mutant strains, and the LD50 values were determined. The expression levels of the immune-related genes in tilapia were analyzed by qRT-PCR. The mutant showed faster growth during the logarithmic growth period (5–10 h) and lower hemolytic activity than the WT strain. Mutant loads in tilapia tissues were significantly lower than those of the WT strain. Mutant strain adhesion to epithelial cells was significantly reduced, it was more easily engulfed by macrophages, and it had decreased intracellular survival. The LD50 of the mutant was 2.06 times higher than that of the WT strain, indicating decreased pathogenicity. Expression levels of immune-related genes IL-1β, IL-6, IFN-γ, and TNF-α in tilapia induced by the mutant were lower than those by the WT strain. In conclusion, the WC1535ΔhsdM mutant exhibited an increased growth rate and decreased hemolytic activity, tissue colonization, and pathogenicity, indicating that HsdM could regulate S. agalactiae growth and pathogenicity. This study provides new insights into the pathogenesis of piscine S. agalactiae.

The role of liver sinusoidal endothelial cells in metabolic dysfunction-associated steatotic liver diseases and liver cancer: mechanisms and potential therapies - Hanjun Mo; Pengfei Yue; Qiaoqi Li; Yinxi Tan; Xinran Yan; Xinyue Liu; Yuanwei Xu; Yingzhe Luo; Suruiya Palihati; Cheng Yi; Hua Zhang; Minlan Yuan; et al. (Angiogenesis, 2025)

Evolution of the lipoxygenase gene family in Pyropia haitanensis and its response to biotic and abiotic stresses - Xiaodong Mo; Zhujun Zhu; Yanrong Li; Jia Li; Xinru Wu; Xiaojun Yan; Haimin Chen (Aquaculture, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

The effect of magnesium oxide on the structure of metakaolin-based geopolymer microspheres and its application in the adsorption of methylene blue dye - Huiying Mo; Leping Liu; Zhaoyu Yang; Yuanxia Lao; Yan He (Journal of Water Process Engineering, 2025)

Microplastics-exposure experience aggravates the accumulation of diarrhetic shellfish toxins (DSTs) in thick-shell mussel Mytilus coruscus through impairing detoxification processes - Kuan-Kuan Yuan; Ying-Ying Yu; Yu-Jie Liu; Xiu-Lin Yang; Yan-Hang Mo; Wei Shi; Guang-Xu Liu; Hong-Ye Li; Wei-Dong Yang (Journal of Hazardous Materials, 2025)

A fully integrated, non-invasive, and multimodal wearable device for sweat stimulation, collection and multiple physiological signals analysis - Yuetao Zhang; Zijie Li; Xuejiao Fan; Yan Liu; Zhiqi Li; Ziwei Zheng; Zixin Lin; Wenshan Zhang; Qingci Mu; Guangquan Mo; Yong Xia; Lei Mou (Chemical Engineering Journal, 2025)

Spatial and temporal distribution, species, and potential source analysis of atmospheric particulate mercury in the Yellow and Bohai seas - Bing Mo; Yan Wang; Xixi Chong; Ruhai Liu; Wen Zheng; Xuyuan Zhou; Dongting Li; Xue Ding; Xianxiang Luo; Fengmin Li (Atmospheric Environment, 2025)

ATP6V1B1 regulates ovarian cancer progression and cisplatin sensitivity through the mTOR/autophagy pathway - Shien Mo; Tingji Liu; Haiqin Zhou; Junning Huang; Ling Zhao; Fangfang Lu; Yan Kuang (Molecular and Cellular Biochemistry, 2025)
Early detection and effective chemotherapy for ovarian cancer, a serious gynecological malignancy, require further progress. This study aimed to investigate the molecular mechanism of ATPase H + -Transporting V1 Subunit B1 (ATP6V1B1) in ovarian cancer development and chemoresistance. Our data show that ATP6V1B1 is upregulated in ovarian cancer and correlated with decreased progression-free survival. Gain- and loss-of-function experiments demonstrated that ATP6V1B1 promotes the proliferation, migration, and invasion of ovarian cancer cells in vitro, while ATP6V1B1 knockout inhibits tumor growth in vivo. In addition, knocking down ATP6V1B1 increases the sensitivity of ovarian cancer cells to cisplatin. Mechanistic studies showed that ATP6V1B1 regulates the activation of the mTOR/autophagy pathway. Overall, our study confirmed the oncogenic role of ATP6V1B1 in ovarian cancer and revealed that ATP6V1B1 promotes ovarian cancer progression via the mTOR/autophagy axis.

Establishing patient-derived tumor organoids of bone metastasis from lung adenocarcinoma reveals the transcriptomic changes underlying denosumab treatment - Xianglin Hu; Huajian Wu; Kewen Hu; Yani Kang; Guoqiang Hua; Mo Cheng; Wangjun Yan; Wending Huang (Clinical & Experimental Metastasis, 2025)

Axin interactor, dorsalization-associated (AIDA) protein promotes appetite and regulates hepatic glycolipid metabolism in Schizothorax prenanti - Run Zhang; Qilang Mo; Aiyu Wang; Xianshu Zhang; Chunjie Chen; Linjie Wang; Yan Wang (Aquaculture, 2025)

Molecular characterization of MSX2 gene and its role in regulating steroidogenesis in yak (Bos grunniens) cumulus granulosa cells - Jun Ma; Gan Yang; Xuan Qin; Luoyu Mo; Xianrong Xiong; Yan Xiong; Honghong He; Daoliang Lan; Wei Fu; Jian Li; Shi Yin (Theriogenology, 2025)

Hyperspectral classification of ancient cultural remains using machine learning - Rongji Luo; Peng Lu; Panpan Chen; Hongtao Wang; Xiaohu Zhang; Shugang Yang; Qingli Wei; Tao Wang; Yongqiang Li; Tao Liu; Deyang Jiang; Jun Du; et al. (Remote Sensing Applications: Society and Environment, 2025)

An eco-friendly ultra-high-performance geopolymer concrete with quaternary binders for 3D printing - Yufei Yan; Mo Zhang; Guowei Ma; Jay Sanjayan (Journal of Cleaner Production, 2025)

A single-layer electrochromic device with long memory effect and ion conduction regulation based on all liquid crystal components - Yigui Xie; Weiran Zhang; Jiaheng Gao; Zhiqiang Yao; Yan Yan; Xiaochang Zou; Guojian Yang; Yu-Mo Zhang; Sean Xiao-An Zhang (Chemical Engineering Journal, 2025)

Map-based cloning revealed BhAPRR2 gene regulating the black peel formation of mature fruit in wax gourd (Benincasa hispida) - Xuling Zhai; Jinqiang Yan; Wenrui Liu; Zheng Li; Zhenqiang Cao; Ying Deng; Renlian Mo; Baochen Wang; Xiaoxin Cheng; Dasen Xie; Biao Jiang (Theoretical and Applied Genetics, 2025)

Spatial distribution, chemical speciation and source apportionment of carbon, nitrogen and phosphorus in surface sediments of northern Beibu Gulf, South China - Jing Guo; Xiaomin Yan; Man Wu; Hengtong Qiu; Wan-Yi Li; Wenlong Huang; Di Wu; Baoming Xue; Guilin Xu; Zihan Pan; Zhiming Mo (Marine Pollution Bulletin, 2024)

AOPPs induces EMT and fibrosis by activating oxidative stress through ERK/p38 MAPK signaling pathway in endometriosis - Xiaoqing Luo; Sixi Wen; Junling Zeng; Jing Liu; Wenting Ye; Jiangpeng Wu; Songyu Huang; Wuwei Xie; Haiping Wen; Yan Sun; Jing Cai; Daidi Mo; et al. (Reproductive Biology, 2024)

Two new species of the subgenus Tipula (Emodotipula) Alexander, 1966 (Diptera, Tipulidae) from southwest China - Qi-Cheng Yang; Li-Ling Mo; Jing Wang; Xiao-Yan Liu; Ding Yang (Journal of Asia-Pacific Entomology, 2024)

Spatiotemporal distribution of the planktonic microbiome and antibiotic resistance genes in a typical urban river contaminated by macrolide antibiotics - Chuanmao Yang; Shiwei Yan; Baihuan Zhang; Xiunan Yao; Jiezhang Mo; Fozia Rehman; Jiahua Guo (Environmental Research, 2024)

The interplay between prehistoric vegetation, climatic fluctuations and anthropogenic activities in Central China - Panpan Chen; Peng Lu; Yan Tian; Ye Li; Hui Wang; Jiaqiang Zhang; Xiangli Zhao; Duowen Mo (CATENA, 2024)

Increase of PCSK9 expression in diabetes promotes VEGFR2 ubiquitination to inhibit endothelial function and skin wound healing - Jian-Jun Gao; Fang-Yuan Wu; Yu-Jia Liu; Le Li; Yi-Jun Lin; Yue-Ting Kang; Yue-Ming Peng; Yi-Fang Liu; Chen Wang; Zhen-Sheng Ma; Yang Cao; Hong-Yu Cao; et al. (Science China Life Sciences, 2024)

Application of Cytochrome P450 Monooxygenases in Plant for Rapid Detection of 2,3,7,8 Tetrachlorodibenzodioxin in the Contaminated Sites - Ho Man Leung; Ka Chun Sung; Lai Yan Woo; Wing Yin Mo; Kwai Chung Cheung; Chi Kin Au; Ken Kin Lam Yung; Wai Chin Li (International Journal of Environmental Research, 2024)

Assessment of Spatial Variability of Polycyclic Aromatic Hydrocarbons (PAHs) in Urban Soils and Fungal Disease Status of Trees Grown in Hong Kong Areas - Ka Chun Sung; Ho Man Leung; Chi Fung Lee; Tohidi Fatemeh; Wing Yin Mo; Lai Yan Woo; Kwai Chung Cheung; Uchenna Ogbonnaya; Ken Kin Lam Yung; Wai Chin Li (International Journal of Environmental Research, 2024)

Impaired inducibility of immune regulatory capacity of peripheral B cells of patients with recurrent pregnancy loss - Fei Ma; Xiaoyang Feng; Shiyu Feng; Jin Liu; Jia Li; Lihua Mo; Lingzhi Xu; Yulei Liu; Jiaman Wu; Pingchang Yang; Yan Ning (Immunologic Research, 2024)

Desertibaculum subflavum gen. nov., sp. nov., a novel member of the family Sneathiellaceae isolated from the Kumtag Desert soil - Chu-Ying Feng; Huan-Huan He; Shuai Li; Zhuo-Huan Zheng; Yi-Jun Mo; Wen-Hui Lian; Chun-Yan Lu; Dong-Ya Zhang; Wen-Jun Li; Lei Dong (Antonie van Leeuwenhoek, 2024)

Exploring the impact of low-carbon city pilot policy on urban ecological welfare performance: A quasi-natural experiment in 282 Chinese cities - Xinmin Zhang; Xiumei Xu; Sheng Pan; Yan Mo; Caihua Dong (Urban Climate, 2024)

Microbial life-history strategies and particulate organic carbon mediate formation of microbial necromass carbon and stabilization in response to biochar addition - Yeye Zhang; Tao Wang; Chun Yan; Yuze Li; Fei Mo; Juan Han (Science of The Total Environment, 2024)

Archaea communities in aerobic granular sludge: A mini-review - Anqi Yan; Zengrui Pan; Yifan Liang; Xinyan Mo; Tao Guo; Jun Li (Science of The Total Environment, 2024)

Evaluation and comparison of iohexol elimination by UV/peroxymonosulfate and UV/persulfate processes: Radical roles, influence factors and iodinated trihalomethanes formation - Chen-Cheng Mo; Fu-Xiang Tian; Bin Xu; Fan Lai; Yu-Qiong Gao; Yan Ma; Zi-Han Feng; Zi-Jian Yao; Dong-Su Bi; Xiao-Jun Hu (Journal of Water Process Engineering, 2024)

Escherichia coli heat-labile enterotoxin B subunit as an adjuvant of mucosal immune combined with GCRV-II VP6 triggers innate immunity and enhances adaptive immune responses following oral vaccination of grass carp (Ctenopharyngodon idella) - Jiyuan Yin; Huiliang Wu; Wei Li; Yingying Wang; Yingying Li; Xubing Mo; Siming Li; Yan Ren; Houjun Pan; Peng Jiang; Qing Wang (Fish & Shellfish Immunology, 2024)

Classification and regression machine learning models for predicting the combined toxicity and interactions of antibiotics and fungicides mixtures - Li-Tang Qin; Jun-Yao Zhang; Qiong-Yuan Nong; Xia-Chang-Li Xu; Hong-Hu Zeng; Yan-Peng Liang; Ling-Yun Mo (Environmental Pollution, 2024)

Overcoming therapeutic limitations in glioblastoma treatment: A nanocomposite inducing ferroptosis and oxeiptosis via Photodynamic therapy - Lei Xu; Jiahe Hu; Xiuwei Yan; Hongtao Zhao; Mo Geng; Jiheng Zhang; Chunxiao Zhou; Zhihui Liu; Bo Li; Shaoshan Hu (Chemical Engineering Journal, 2024)

Integrating DNA logic computation and Self-Replication on nanospheres for amplified detection of Dual miRNAs - Liuting Mo; Yan Hong; Rongzheng Yuan; Mingxiu Mo; Chan Yang; Weiying Lin (Chemical Engineering Journal, 2024)

Single-cell immune landscape of measurable residual disease in acute myeloid leukemia - Xiaodong Mo; Weilong Zhang; Guomei Fu; Yingjun Chang; Xiaohui Zhang; Lanping Xu; Yu Wang; Chenhua Yan; Mengzhu Shen; Qiuxia Wei; Changjian Yan; Xiaojun Huang (Science China Life Sciences, 2024)

Improving key gene expression and di-n-butyl phthalate (DBP) degrading ability in a novel Pseudochrobactrum sp. XF203 by ribosome engineering - Yunchang Xie; Nai-Xian Feng; Li Huang; Miaoer Wu; Cheng-Xuan Li; Fantao Zhang; Yunhong Huang; Quan-Ying Cai; Lei Xiang; Yan-Wen Li; Hai-Ming Zhao; Ce-Hui Mo (Science of The Total Environment, 2024)

Microplastics positively mediate soil multifunctionality in dryland - Peng-Yang Wang; Ze-Ying Zhao; Kadambot H.M. Siddique; Xiao-Bin Xiong; Hong-Yan Tao; Yue Ma; Fei Mo; Yinglong Chen; Yajie Song; William R. Burch; Baoluo Ma; Song Wang; et al. (Resources, Conservation and Recycling, 2024)

The long-term effects of transformation and upgrading policies on the market performance of China's coal-fire power generation industry - Yan Li; Kailu Zhang; Bojiao Mu; Xinran Mo (Mitigation and Adaptation Strategies for Global Change, 2024)

Root-associated bacterial communities of vegetable Brassica parachinensis enrich pollutant-degrading taxa and functions for enhancing phthalate dissipation - Zhen Wang; Yu-Hong Huang; Minying He; Yan Hu; Xiaohan Xu; Quan-Ying Cai; Ce-Hui Mo; Huixiong Lü (Applied Soil Ecology, 2024)

Automatic identification of cirques based on RetinaNet model and pseudo-color image fusion method - Zhenxin Shi; Guiquan Mo; Yurong Cui; Libo Yan; Yunshan Lu; Lina Hou; Lansong Lv; Huixuan Li (Advances in Space Research, 2024)

Pharmacological Activities of Brevilin A: A Mini-Review - Heng Yang; Yan Wu; Minyi Mo; Lizhi Zhu; Duo Zheng (Current Pharmacology Reports, 2024)

Quantitative detection of Pythium porphyrae and Pythium chondricola (Oomycota), the causative agents of red rot disease in Pyropia farms in China - Jie Liu; Sudong Xia; Huichao Yang; Zhaolan Mo; Jie Li; Yongwei Yan (Algae, 2024)
Red rot disease is one of the notorious algal diseases that threaten the cultivation of Pyropia in China, and two Pythium pathogens , i.e., Pythium porphyrae and P. chondricola , have been reported as causative agents. To monitor the pathogens, a fluorescent quantitative polymerase chain reaction (PCR) method was developed to quantitatively detect their abundance. Using overlapping PCR and pathogen-specific primer pairs, two pathogen-specific fragments were concatenated to construct an internal standard plasmid, which was used for quantification. For zoospores of known numbers, the results showed that this method can detect as less as 100 and 10 zoospores mL -1 in a 200 mL solution for P. porphyrae and P. chondricola , respectively. Using monthly collected seawater at 10 sites in Haizhou Bay, a typical aquaculture farm in China, a significantly higher temperature and a significantly lower salinity were determined in December 2021. P. porphyrae was determined to be more abundant than P. chondricola , though with similar temporal distribution patterns from December 2021 to February 2022. When a red rot disease occurred in December 2021, the two pathogens were significantly more abundant at two infected sub-sites than the uninfected sub-site within both seawater and sediment, though they were all significantly more enriched in sediment than in seawater. The present method provides the capability to quantify and compare the abundance of two pathogens and also has the potential to forecast the occurrence of red rot disease, which is of much significance in managing and controlling the disease.

Biostimulation accelerates landfill stabilization and resource utilization efficiency, providing feasible technical support for the overall lifecycle management of landfills - Mingxing Li; Hui Jiang; Xiang Mo; Ruiding Li; Lifeng Liu; Wenchan Wu; Wendong Liu; Yong Xie; Xing Li; Fangfang Yan; Zhongping Qiu (Chemosphere, 2024)

CsERF003 enhanced peel coloration by promoting both chlorophyll degradation and carotenoid accumulation in citrus - Ranran Wei; Yan Lu; Zhijing Mo; Quan Sun; Pengtao Yue; Zongzhou Xie; Junli Ye; Xiuxin Deng (Plant Science, 2024)

Mining flotation reagents: Quantitative and robust analysis of metal-xanthate complexes in water - Wen-Jun Wu; Qing-Jun Zheng; Jing-Wen Liang; Hai-Ming Zhao; Bai-Lin Liu; Yan-Wen Li; Nai-Xian Feng; Quan-Ying Cai; Lei Xiang; Ce-Hui Mo; Qing X. Li (Journal of Hazardous Materials, 2024)

Seeking a pathway towards a more sustainable human-water relationship by coupled model – From a perspective of socio-hydrology - Jingyu Lyu; Shuhong Mo; Kaixin Jiang; Siyu Yan (Journal of Environmental Management, 2024)

Simultaneous biodegradation of polycyclic aromatic hydrocarbons and phthalates by bacterial consortium and its bioremediation for complex polluted soil and sewage sludge - Yao-Si Chen; Yu-Hong Huang; Huixiong Lü; Hai-Ming Zhao; Lei Xiang; Hui Li; Ce-Hui Mo; Yan-Wen Li; Quan-Ying Cai (Bioresource Technology, 2024)

Spatiotemporal changes of urban heat island effect relative to land surface temperature: a case study of Jinan City, China - Guiquan Mo; Libo Yan; Zhiyong Li; Zongyao Wang; Sixuan Chen; Huixuan Li; Shuwei Zheng; Yurong Cui (Environmental Science and Pollution Research, 2024)

Hunnivirus structural protein VP2 inhibits beta interferon production by targeting the IRF3 essential modulator - Xinyue Zhu; Qinting Dong; Kang Zhang; Yanlin Zou; Guangxin Zhang; Yiyang Du; Xiaoke Mo; Aoqi Wu; Kang Ouyang; Ying Chen; Zuzhang Wei; Yifeng Qin; et al. (Veterinary Microbiology, 2024)

Glycerophospholipid metabolism changes association with ozone exposure - Yi Zhang; Jicheng Gong; Xinyan Hu; Linchen He; Yan Lin; Junfeng Zhang; Xin Meng; Yinping Zhang; Jinhan Mo; Drew B. Day; Jianbang Xiang (Journal of Hazardous Materials, 2024)

A novel algorithm to extrapolate ultraviolet absorption of chromophoric dissolved organic matter from remote sensing ocean color - Zhongli Liu; Shansheng Mo; Fei Liu; Gregory Korshin; Mingquan Yan (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Teleost-specific TLR23 in Takifugu rubripes recruits MyD88 to trigger ERK pathway and promotes antibacterial defense - Yu-ting Du; Hong-qiang Zhang; Yan Li; Xue-peng Li; Zeng-zhi Yuan; Mo-fei Li (Fish & Shellfish Immunology, 2024)

Evaluating warming trend over the tibetan plateau based on remotely sensed air temperature from 2001 to 2020 - Yan Xin; Yongming Xu; Xudong Tong; Yaping Mo; Yonghong Liu; Shanyou Zhu (Climatic Change, 2024)

Development of real‐time recombinase polymerase amplification ( RPA ) and RPA combined with lateral flow dipstick ( LFD ) assays for the rapid and sensitive detection of cyprinid herpesvirus 3 - Yingying Li; Ruifan Li; Xubing Mo; Yingying Wang; Jiyuan Yin; Sven M. Bergmann; Yan Ren; Houjun Pan; Cunbin Shi; Defeng Zhang; Qing Wang (Journal of Fish Diseases, 2024)
In this issue, we established rapid, cost‐effective, and simple detection methods including recombines polymerase amplification with lateral flow dipstick (RPA‐LFD) and real‐time RPA for cyprinid herpesvirus 3(CyHV‐3), and evaluated their sensitivity, specificity, and applicability, the real‐time RPA method could achieve sensitive diagnosis of CyHV‐3 within 1.3 copies per reaction, respectively. The real‐time RPA method is 10‐fold more sensitive than RPA‐LFD method. The exact number of CyHV‐3 can be calculated in each sample by real‐time RPA. The sera from koi also can be tested in these methods. In addition, no cross‐reaction was observed with other related pathogens, including carp oedema virus (CEV), spring viraemia of carp virus (SVCV), cyprinid herpesvirus 1(CyHV‐1), cyprinid herpesvirus 2(CyHV‐2), type I grass carp reovirus (GCRV‐I), type II GCRV (GCRV‐II), type III GCRV (GCRV‐III), and Aeromonas hydrophila.

Root-zone regulation and longitudinal translocation cause intervarietal differences for phthalates accumulation in vegetables - Bogui Pan; Xiaoqiong Zhu; Li Huang; Kunzheng Cai; Yan-Wen Li; Quan-Ying Cai; Nai-Xian Feng; Ce-Hui Mo (Chemosphere, 2024)

Soil-dwelling grub larvae of Protaetia brevitarsis biodegrade polystyrene: Responses of gut microbiome and host metabolism - Jie Jiang; Haowen Xu; Xiaomu Cao; Yuqing Liang; Aoyun Mo; Xuelong Cao; Yan Liu; Mark Eric Benbow; Craig S. Criddle; Wei-Min Wu; Defu He (Science of The Total Environment, 2024)

Polymer chain extenders induce significant toxicity through DAF-16 and SKN-1 pathways in Caenorhabditis elegans: A comparative analysis - Aoyun Mo; Yuqing Liang; Xiaomu Cao; Jie Jiang; Yan Liu; Xuelong Cao; Yuping Qiu; Defu He (Journal of Hazardous Materials, 2024)

Plant-Cell mediated synthesis of MnCo2O4 nanoparticles and their activation of peroxymonosulfate to remove Tetracycline - Jialu Ji; Qi Zhang; Hesu Mo; Zhongfei Ren; Yan Lin; Zhigang Chen; Tiina Leiviskä; Zhengying Wu (Chemical Engineering Journal, 2024)

Germination and growth of corn submitted to sowing and cultivation management by subsurface drip irrigation in the North China Plain - Yan Mo; Yanqun Zhang; Dan Wang; Jiandong Wang; Guangyong Li; Shihong Gong; Xiaoyan Gao (Irrigation Science, 2024)

The autophagy-mediated mechanism via TSC1/mTOR signaling pathway in thiram-induced tibial dyschondroplasia of broilers - Chuxian Quan; Shimeng Zhou; Yan Zhang; Muhammad Fakhar-e-Alam Kulyar; Saisai Gong; Shah Nawaz; Ahmed Ezzat Ahmed; Quan Mo; Jiakui Li (Science of The Total Environment, 2024)

Congener-specific fate and impact of microcystins in the soil-earthworm system - Bai-Lin Liu; Peng-Fei Yu; Jing-Jie Guo; Li-Si Xie; Xiang Liu; Yan-Wen Li; Lei Xiang; Hai-Ming Zhao; Nai-Xian Feng; Quan-Ying Cai; Ce-Hui Mo; Qing X. Li (Journal of Hazardous Materials, 2024)

Physiological and genetic responses of the benthic dinoflagellate Prorocentrum lima to polystyrene microplastics - Si-Yuan Xu; Yan-Hang Mo; Yu-Jie Liu; Xiang Wang; Hong-Ye Li; Wei-Dong Yang (Harmful Algae, 2024)

Response of Leaf Gas Exchange Parameters to Mulching Materials in Wheat Field was Mediated by Stomatal Morphology and ABA Content - Shanshan Qin; Yanqun Zhang; Jiandong Wang; Chuanjuan Wang; Yan Mo; Shihong Gong; Baozhong Zhang (Journal of Plant Growth Regulation, 2024)

Differentiation of bone marrow mesenchymal stem cells into Leydig-like cells with testicular extract liquid in vitro - Rong Hua; Fang-Fang Liang; Fang-Qiang Gong; Hua Huang; Yi-Chen Xu; Min He; Yan-Hua Fang; Ya-Shu Wei; Wei-Wei Zhou; Arshad Mehmood; Yi Mo; Zhong Lin (In Vitro Cellular & Developmental Biology - Animal, 2024)

A universal model to predict yields of THMs and HAAs based on UV–Visible absorption spectra - Yang Deng; Shansheng Mo; Gregory V. Korshin; Mingquan Yan (Water Research, 2024)

Community stability of free-living and particle-attached bacteria in a subtropical reservoir with salinity fluctuations over 3 years - Xue Yan; Shuzhen Li; Mamun Abdullah Al; Yuanyuan Mo; Jun Zuo; Hans-Peter Grossart; Hongteng Zhang; Yigang Yang; Erik Jeppesen; Jun Yang (Water Research, 2024)

Exposure to microplastics renders immunity of the thick-shell mussel more vulnerable to diarrhetic shellfish toxin-producing harmful algae - Kuan-Kuan Yuan; Ying-Ying Yu; Yan-Hang Mo; Yu-Jie Liu; Wei-Xia Zhang; Jin-Jin Lv; Wei Shi; Guang-Xu Liu; Hong-Ye Li; Wei-Dong Yang (Science of The Total Environment, 2024)

Toxic interactions at the physiological and biochemical levels of green algae under stress of mixtures of three azole fungicides - Li-Tang Qin; Yu-Xue Lei; Min Liu; Hong-Hu Zeng; Yan-Peng Liang; Ling-Yun Mo (Science of The Total Environment, 2024)

Early Paleocene diorite and bimodal dykes from the Dagze region, southern Lhasa Terrane: Tectonic implications for the late-stage of Neo-Tethyan subduction - Yan Tang; Zhidan Zhao; Xiaowei Li; Zhenzhen Wang; Ningyuan Qi; Dong Liu; Qing Wang; Xuanxue Mo (Lithos, 2024)

Iron complex regulated synergistic effect between the current and peroxymonosulfate enhanced ultrafast oxidation of perfluorooctanoic acid via free radical dominant electrochemical reaction - Meng Li; Peitong Cen; Lei Huang; Jia Yan; Shaoqi Zhou; King Lun Yeung; Ce-Hui Mo; Hongguo Zhang (Journal of Hazardous Materials, 2024)

Biodegradation of phthalate acid esters and whole-genome analysis of a novel Streptomyces sp. FZ201 isolated from natural habitats - Nai-Xian Feng; Da-Wei Li; Fei Zhang; Hui Bin; Yi-Tong Huang; Lei Xiang; Bai-Lin Liu; Quan-Ying Cai; Yan-Wen Li; De-Lin Xu; Yunchang Xie; Ce-Hui Mo (Journal of Hazardous Materials, 2024)

Impacts of biochar aging on its interactions with As(III) and the combined cytotoxicity - Jian Liu; Zihui Huo; Yucong Mo; Xinxin Huang; Yuting Wen; Xiliang Yan; Weizhen Liu; Bing Yan; Hongyu Zhou (Environmental Research, 2024)

Bioprospecting of Chlamydomonas reinhardtii for boosting biofuel-related products production based on novel aggregation-induced emission active extracellular polymeric substances nanoprobes - Yan Wang; Yubing Hu; Jiezhang Mo; Tin Yan Wong; Jingjing Liu; Parodi Alessandro; Ben Zhong Tang; Wen-Xiong Wang; Neng Yan (Bioresource Technology, 2024)

Correction to: Efects of Manganese and Iron, Alone or in Combination, on Apoptosis in BV2 Cells - Yuan-yuan Fang; Cui-liu Gan; Jian-chao Peng; Yu-han Xie; Han-xiao Song; Ya-qi Mo; Shi-yan Ou; Michael Aschner; Yue-ming Jiang (Biological Trace Element Research, 2024)

Effects of Manganese and Iron, Alone or in Combination, on Apoptosis in BV2 Cells - Yuan-yuan Fang; Cui-liu Gan; Jian-chao Peng; Yu-han Xie; Han-xiao Song; Ya-qi Mo; Shi-yan Ou; Michael Aschner; Yue-ming Jiang (Biological Trace Element Research, 2024)

Ultrasensitive cortisol electrochemical immunosensor amplifying by Au single-atom nanozymes and HRP enzymes - Yongling Du; Min Guo; Yan Chen; Xiaohui Mo; Junlei Cao; Fangdi Hu (Analytica Chimica Acta, 2024)

Monitoring of key Camellia Oleifera phenology features using field cameras and deep learning - Haoran Li.; Enping Yan; Jiawei Jiang; Dengkui Mo (Computers and Electronics in Agriculture, 2024)

Ratiometric SERS quantification of SO2 vapor based on Au@Ag-Au with Raman reporter as internal standard - Yu Lu; Xiufang Mo; Geng Zhu; Yan Huang; Yingchao Wang; Zhenzhong Yang; Liqiong Gao; Guofang Shen; Yi Wang; Xiangwei Zhao (Journal of Hazardous Materials, 2024)

Microbial consortium degrading of organic pollutants: Source, degradation efficiency, pathway, mechanism and application - Huixiong Lü; Jia-Lu Wei; Guang-Xuan Tang; Yao-Si Chen; Yu-Hong Huang; Ruiwen Hu; Ce-Hui Mo; Hai-Ming Zhao; Lei Xiang; Yan-Wen Li; Quan-Ying Cai; Qing X. Li (Journal of Cleaner Production, 2024)

Efficient trimethoprim removal via cooperation of radical and non-radical pathways in UV/peroxymonosulfate: Kinetics, mechanisms and disinfection by-products-associated risks - Chen-Cheng Mo; Fu-Xiang Tian; Bin Xu; Juan Wang; Yu-Qiong Gao; Dong-Su Bi; Bo Wang; Xing-Yan Mu; Xiao-Jun Hu (Journal of Environmental Chemical Engineering, 2024)

Effects of heterovalent ions doping-induced oxygen octahedral distortion and defect chemical change on piezoelectric characteristics and thermal stability of PHT-PIN ceramics - Yun Qiao; Longlong Wang; Dongyan Zhang; Zhimin Li; Maolin Zhang; Li Jin; Mo Zhao; Yangxi Yan (Chemical Engineering Journal, 2024)

Covalently bonded MXene@Antimonene heterostructure anode for fast lithium-ion storage - Zheng Bo; Zhouwei Zheng; Yanzhong Huang; Pengpeng Chen; Jianhua Yan; Kefa Cen; Runwei Mo; Huachao Yang; Kostya (Ken) Ostrikov (Chemical Engineering Journal, 2024)

Preconcentrating sensor systems toward indoor low-concentration VOC detection by goal-oriented, sequential, inverse design strategy - Yan Wang; Zhuo Chen; Qiwei Chen; Enze Tian; Ning Han; Jinhan Mo (Building and Environment, 2024)

Heterologous expression of taxane genes confers resistance to fall armyworm in Nicotiana benthamiana - Zhenlu Xu; Yaohua Zhai; Huimin Chang; Da Yan; Pengliang Ge; Guangming Ren; Lijun Zhang; Ye Yuan; Ruoyan Wang; Wentao Li; Fuguang Li; Maozhi Ren; et al. (Plant Cell Reports, 2024)

Infant Exposure and Risk Assessment of Organophosphorus Flame Retardants in Human Breast Milk from The Southeast City, China - Quan Zhang; Yan Wang; Jianlin Lou; Zeteng Ying; Xunjie Mo; Shu Lin (Exposure and Health, 2024)

Micro(nano)plastics in human urine: A surprising contrast between Chongqing's urban and rural regions - Xuan Song; Tian Chen; Zongwen Chen; Lixia Du; Xihong Qiu; Yuxin Zhang; Yan Li; Yu Zhu; Zhongyou Tan; Yunbo Mo; Xiaoqian Feng (Science of The Total Environment, 2024)

Root-associated bacteria strengthen their community stability against disturbance of antibiotics on structure and functions - Yu-Hong Huang; Yu-Jie Yang; Jie-Yu Li; Huixiong Lü; Hai-Ming Zhao; Lei Xiang; Hui Li; Ce-Hui Mo; Yan-Wen Li; Quan-Ying Cai; Qing X. Li (Journal of Hazardous Materials, 2024)

Structural, functional and antioxidant properties of Lentinus edodes protein hydrolysates prepared by five enzymes - Shu-Jing Bing; Xing-Shuo Chen; Xin Zhong; Ying-Qiu Li; Gui-Jin Sun; Chen-Ying Wang; Yan Liang; Xiang-Zhong Zhao; Dong-Liang Hua; Lei Chen; Hai-Zhen Mo (Food Chemistry, 2024)

Bright long persistent luminescence in cluster-based MOFs derived from intra-ligand charge transfer characteristic - Jun-Ting Mo; Zheng Wang; Xian-Yan Xu; Fenske Dieter; Mei Pan; Cheng-Yong Su (Chemical Engineering Journal, 2024)

Endothelial extracellular vesicles induce acute lung injury via follistatin-like protein 1 - Hao-Xiang Yuan; Ya-Ting Chen; Yu-Quan Li; Yan-Sheng Wang; Zhi-Jun Ou; Yan Li; Jian-Jun Gao; Meng-Jie Deng; Yuan-Kai Song; Li Fu; Hong-Bo Ci; Feng-Jun Chang; et al. (Science China Life Sciences, 2024)

Effects of ridge tillage and peanut growth on the surface–subsurface runoff generation and soil loss in the red soil sloping farmland of southern China - Kenan Deng; Zhao Liu; Xudong Han; Yan Zhu; Guanfang Sun; Minghao Mo (Journal of Soils and Sediments, 2024)

Response and adaptation of rhizosphere microbiome to organic pollutants with enriching pollutant-degraders and genes for bioremediation: A critical review - Huixiong Lü; Guang-Xuan Tang; Yu-Hong Huang; Ce-Hui Mo; Hai-Ming Zhao; Lei Xiang; Yan-Wen Li; Hui Li; Quan-Ying Cai; Qing X. Li (Science of The Total Environment, 2024)

Insights into the molecular network underlying phytotoxicity and phytoaccumulation of ciprofloxacin - Hai-Ming Zhao; He-Biao Huang; Zhen-Xuan Zhan; Yao-Yao Ye; Ji-Liang Cheng; Lei Xiang; Yan-Wen Li; Quan-Ying Cai; Yunchang Xie; Ce-Hui Mo (Science of The Total Environment, 2024)

Evaluation of the fate of wastewater effluent organic matter in receiving water: Effect of sequential photochemical and biological processes - Lei Zheng; Feng Xiao; Xinyi Zhang; Yang Deng; Shansheng Mo; Zhongli Liu; Xin Gu; Norbert Hertkorn; Gregory V. Korshin; Mingquan Yan (Journal of Hazardous Materials, 2024)

Corrigendum to “Over-expression of miR-100 is responsible for the low-expression of ATM in the human glioma cell line: M059J” [DNA Repair 9 (2010) 1170-1175] - Wooi Loon Ng; Dan Yan; Xiangming Zhang; Yin-Yuan Mo; Ya Wang (DNA Repair, 2024)

High-density lipoprotein regulates angiogenesis by affecting autophagy via miRNA-181a-5p - Bi-Ang Kang; Hua-Ming Li; Ya-Ting Chen; Meng-Jie Deng; Yan Li; Yue-Ming Peng; Jian-Jun Gao; Zhi-Wei Mo; Jia-Guo Zhou; Zhi-Jun Ou; Jing-Song Ou (Science China Life Sciences, 2024)

Deep electrical structures of Qinzhou-Fangcheng Junction Zone in Guangxi and seismogenic environment of the 1936 Lingshan M6¾ earthquake - Bin Zhou; Chunheng Yan; Yan Zhan; Xiangyu Sun; Sha Li; Xiang Wen; Yajun Mo; Yongdong Yuan; Yuan Yuan; Meili Huang (Science China Earth Sciences, 2024)

Efficient adsorption of Cu2+ and Cd2+ from groundwater by MgO-modified sludge biochar in single and binary systems - Yan Wang; Xianrong Meng; Shanhu Wang; Yuanye Mo; Wei Xu; Yang Liu; Weilin Shi (Environmental Science and Pollution Research, 2024)

Application and evaluation of probiotics against red rot disease in Pyropia - Peiwen Weng; Huichao Yang; Zhaolan Mo; Wenbin Zhang; Yongwei Yan; Xiaojun Rong; Jie Li (Aquaculture, 2024)

Characteristics of microplastic-derived dissolved organic matter and its binding with pharmaceuticals unveiled by fluorescence spectroscopy and two-dimensional correlation spectroscopy - Caixia Yan; Xiao Wang; Minghua Nie; Xiting Mo; Mingjun Ding; Jie Chen; Yi Yang (Science of The Total Environment, 2024)

Binding interaction of environmental DNA with typical emerging perfluoroalkyl acids and its impact on bioavailability - Chao Qin; Lei Xiang; Yi-Ze Wang; Peng-Fei Yu; Can Meng; Yan-Wen Li; Hai-Ming Zhao; Xiaojie Hu; Yanzheng Gao; Ce-Hui Mo (Science of The Total Environment, 2024)

Basin-scale reconstruction of late Pleistocene-Holocene fluvial landform evolution and its mechanisms in transitional areas between Taihang Mountain and North China Plain - Yan Tian; Panpan Chen; Peng Lu; Ye Li; Hui Wang; Liang Zhou; Xiaohu Zhang; Shugang Yang; Xingguo Zhang; Xiaoyu Chai; Haiguo Zhai; Min Liu; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Quaternary evolution of the Meiji Atoll (Mischief Reef) in the southern South China Sea - Feng Wu; Xinong Xie; Wen Yan; Youhua Zhu; Beichen Chen; Jianuo Chen; Mo Zhou (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Size and concentration effects of polythene plastic residues on soil physiochemical traits and maize productivity: A three-year appraisal - Ze-Ying Zhao; Peng-Yang Wang; Xiao-Bin Xiong; Momena Irum; Fei Mo; Jing Cao; Ning Wang; Hong-Yan Tao; Meng Hao; Song Wang; Kai-Wen Xiao; Fang-Kun Yang; et al. (Journal of Cleaner Production, 2024)

Boosting solar photothermal synergy for efficient overall water splitting based on Mg, Al codoped and Rh/Cr2O3/CoOOH coloaded SrTiO3 - Xuan Zhu; Yan Liu; Menglin Wang; Li Zhang; Qiaoli Li; Entao Zhang; Hongfen Mo; Yuan Gao; Chenyu Xu; Yanwei Zhang (Chemical Engineering Journal, 2024)

Determination of uptake rates of volatile organic compounds by 24-hour passive sampling and their application in enclosed ship cabin environments - Tao Yu; Yan Wang; Longfei Chen; Wenjun Leng; Yue Shi; Bencheng Lin; Juntao Zhao; Zhiyuan Wang; Jinhan Mo; Cong Liu (Building and Environment, 2024)

Climate-shaped vegetation dominated the spatial pattern of the Bowen ratio over terrestrial ecosystems in China - Mingyu Sun; Guirui Yu; Zhi Chen; Tianxiang Hao; Meng Yang; Xianjin Zhu; Weikang Zhang; Lang Han; Zhaogang Liu; Lexin Ma; Xiaojun Dou; Yuan Yao; et al. (Agricultural and Forest Meteorology, 2024)

Characterizing photochemical production carboxyl content of dissolved organic matters using absorbance spectroscopy combined with FT-ICR MS - Zizhuo Wei; Na Li; Xinyi Zhang; Lei Zheng; Shansheng Mo; Gregory Korshin; Qingwei Li; Mingquan Yan (Chemosphere, 2023)

The spatial patterns and driving mechanisms of blue carbon ‘loss’ and ‘gain’ in a typical mangrove ecosystem: A case study of Beihai, Guangxi Province of China - Zhenxi Xie; Haonan Li; Yuan Yuan; Wei Hu; Gang Luo; Longtian Huang; Mo Chen; Weimei Wu; Guiling Yan; Xiang Sun (Science of The Total Environment, 2023)

Iron and nitrogen modified sludge biochar efficiently activated persulfate for mineralization of sulfamethoxazole in groundwater - Shanhu Wang; Xianrong Meng; Xingyu Yan; Yan Wang; Yuanye Mo; Yonghao Chen; Wei Xu; Weilin Shi (Journal of Environmental Chemical Engineering, 2023)

Enhanced CO2 adsorption performance by crystal defect method of multi-level pore Mg-MOF-74 using organic acids - Guanhua Zhang; Shaocong Mo; Hongtao Xu; Xiaoyu Yan; Binlin Dou; Guomin Cui; Qiguo Yang; Wei Lu (Gas Science and Engineering, 2023)

Effect of greenhouse gas emissions on the life cycle of biomass energy production and conversion under different straw recycling modes - Yan Zhou; Guoqing Xu; Haiyan Li; Yingshan Chen; Xianghui Xu; Mo Li (Environmental Research, 2023)

Developing positively surface-charged carbon dots as “semiconductor electrolyte” for photo-electrochemical H2O2 production based on oxygen reduction - Yong-Shuai Zhang; Hui-Min Duan; Na Wang; Dong-Dong Wei; Liu-Meng Mo; Ning Wang; Xin-Pei Wang; Shuang-Lei Lei; Yuan Zhang; Hong-Yan Wang (Chemical Engineering Journal, 2023)

Overview and countermeasures of cancer burden in China - Yian Wang; Qijia Yan; Chunmei Fan; Yongzhen Mo; Yumin Wang; Xiayu Li; Qianjin Liao; Can Guo; Guiyuan Li; Zhaoyang Zeng; Wei Xiong; He Huang (Science China Life Sciences, 2023)

Exploring the mechanism by which quercetin re-sensitizes breast cancer to paclitaxel: network pharmacology, molecular docking, and experimental verification - Ye Yang; Jiaoyan Yan; Jian Huang; Xiangyi Wu; Yan Yuan; Yan Yuan; Shu Zhang; Fei Mo (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Interpreting pH-Dependent Differential UV/VIS Absorbance Spectra to Characterize Carboxylic and Phenolic Chromophores in Natural Organic Matter - Chenyang Zhang; Shansheng Mo; Zhongli Liu; Bingya Chen; Gregory Korshin; Norbert Hertkorn; Jinren Ni; Mingquan Yan (Water Research, 2023)

Comparison of gap-filling methods for producing all-weather daily remotely sensed near-surface air temperature - Yaping Mo; Yongming Xu; Yonghong Liu; Yan Xin; Shanyou Zhu (Remote Sensing of Environment, 2023)

A pilot study on glutamate receptor and carrier gene variants and risk of childhood autism spectrum - Jun Liu; Jing Yan; Fei Qu; Weiming Mo; Hong Yu; Pingfang Hu; Zengyu Zhang (Metabolic Brain Disease, 2023)

Dyslexia-related loci are significantly associated with language and literacy in Chinese–English bilingual Hong Kong Chinese twins - Cheuk Yan Chung; Dora Jue Pan; Silvia Paracchini; Wenxuan Jiang; Hon-Cheong So; Catherine McBride; Urs Maurer; Mo Zheng; Kwong Wai Choy (Human Genetics, 2023)

Identification of Diagnostic Markers in Synovial Tissue of Osteoarthritis by Weighted Gene Coexpression Network - Yun-Sen Zhu; Hong Yan; Ting-Ting Mo; Jiang-Nan Zhang; Chang Jiang (Biochemical Genetics, 2023)

USP14 Regulates ATF2/PIK3CD Axis to Promote Microvascular Endothelial Cell Proliferation, Migration, and Angiogenesis in Diabetic Retinopathy - Fu-Tao He; Xiao-Lin Fu; Mo-Han Li; Chun-Yan Fu; Jian-Zhi Chen (Biochemical Genetics, 2023)

Evolutionary characterization and pathogenicity of Getah virus from pigs in Guangdong Province of China - Jinghua Pan; Haoquan Zhang; Xiuqiao Chen; Mengyi Zeng; Hui Han; Yajing Guo; Jiaming Li; Shicheng Luo; Guangzhi Yan; Shengnan Chen; Meilian Mo; Mingjie Liu; et al. (Archives of Virology, 2023)

Molecular cloning and characterization of STC1 gene and its functional analyses in yak (Bos grunniens) cumulus granulosa cells - Xue Yang; Jun Ma; Luoyu Mo; Yan Xiong; Xianrong Xiong; Daoliang Lan; Wei Fu; Shi Yin (Theriogenology, 2023)

Early Paleozoic subduction imprints of the Proto-Tethys Ocean: Evidence from the Appinite–Diorite–Granodiorite complex in East Kunlun, Northern Tibet - Yang-Ming Hu; Xiao-Wei Li; Xuan-Xue Mo; Lin Li; Kai Wang; Bing-Zhang Wang; Xiao-Ping Gong; Guo-Chen Dong; Yan-Bin Liu (Lithos, 2023)

GRPR down-regulation inhibits spermatogenesis through Ca2+ mediated by PLCβ/IP3R signaling pathway in long-term formaldehyde-exposed rats - Yan-qi Yang; Rui-fang Sun; Pan Ge; Wen-Xing Li; Xiang Zhang; Jian Zhang; Lu Ye; Nan Zhang; Si-yu Wang; Mo-qi Lv; Dang-xia Zhou (Food and Chemical Toxicology, 2023)

Hierarchical diffusion pathways into VOC adsorption films by direct ink writing and ammonium carbonate treatment - Qiwei Chen; Zhuo Chen; Yan Wang; Enze Tian; Jinhan Mo (Chemical Engineering Journal, 2023)

Genesis and controlling factors of Cenozoic dolostones in the South China Sea: a case study from core Nanke-1 in the Nansha Islands - Mo Zhou; Feng Wu; Xinong Xie; Wen Yan (Marine Geophysical Research, 2023)

Chinese “Scholars’ Stones”: a Potential Heritage Stone Resource Under Strong Anthropogenic Pressure - Weilun Kong; Yunhuai Li; Kongliang Li; Mo Chen; Yan Peng; Degao Wang; Lijun Chen; Linghong Ge; Pei Yang; Huiju Wu; Jifei Hu (Geoheritage, 2023)

Bioremediation of aniline aerofloat wastewater at extreme conditions using a novel isolate Burkholderia sp. WX-6 immobilized on biochar - Jin-Cheng Ye; Qiu-Shi Zhao; Jin-Wei Liang; Xiao-Xiao Wang; Zhen-Xuan Zhan; Huan Du; Ji-Liang Cheng; Lei Xiang; Nai-Xian Feng; Bai-Lin Liu; Yan-Wen Li; Hui Li; et al. (Journal of Hazardous Materials, 2023)

IL8 of Takifugu rubripes is a chemokine that interacts with peripheral blood leukocytes and promotes antibacterial defense - Hong-qiang Zhang; Xiao-yan Jin; Xue-peng Li; Mo-fei Li (Fish & Shellfish Immunology, 2023)

Mitigating the adverse effects of Aflatoxin B1 in LMH, IPEC-J2 and 3D4/21 cells by a novel integrated agent - Yi-Xin Mo; Meng-Ling Ruan; Jie Wang; Ying Liu; Yuan-Yuan Wu; Guan-Lin Wang; Yan-Ming Han; Hai-Feng Wan; Dessalegn Lamesgen; Kamil Kuča; Jiang Deng; Lv-Hui Sun (Food and Chemical Toxicology, 2023)

The Mechanism of Immobilization of Cd(II) by Phosphate-Solubilizing Bacteria Bacillus sp. B19 - Si-Yi Liu; Qiang Pu; Tian-Jin Mo; Guixiang Peng; Yan Sun; Yulong Zhang; Jinjin Wang; Yongtao Li; Hui-Juan Xu (Water, Air, & Soil Pollution, 2023)

Superresolution live-cell imaging reveals that the localization of TMEM106B to filopodia in oligodendrocytes is compromised by the hypomyelination-related D252N mutation - Shijia Xing; Xiaolu Zheng; Huifang Yan; Yanquan Mo; Ruoyu Duan; Zhixing Chen; Kunhao Wang; Kai Gao; Tongsheng Chen; Shiqun Zhao; Jingmin Wang; Liangyi Chen (Science China Life Sciences, 2023)

Thickness effects of polyethylene and biodegradable film residuals on soil properties and dryland maize productivity - Aimee Grace Uzamurera; Ze-Ying Zhao; Peng-Yang Wang; Yong-Xian Wei; Fei Mo; Rui Zhou; Wen-Li Wang; Fazal Ullah; Aziz Khan; Xiao-Bin Xiong; Meng-Ying Li; Kiprotich Wesly; et al. (Chemosphere, 2023)

Ram sperm cryopreservation disrupts metabolism of unsaturated fatty acids - Jones Ofosu; Moses Addo Nartey; Xianhong Mo; Jiangfeng Ye; Yan Zhang; Changjun Zeng; Ming Zhang; Yi Fang; Guangbin Zhou (Theriogenology, 2023)

The PIWI-specific insertion module helps load longer piRNAs for translational activation essential for male fertility - Xin Wang; Di-Hang Lin; Yue Yan; An-Hui Wang; Jiaoyang Liao; Qian Meng; Wen-Qing Yang; Heng Zuo; Min-Min Hua; Fengjuan Zhang; Hongwen Zhu; Hu Zhou; et al. (Science China Life Sciences, 2023)

New insights into the effects of antibiotics and copper on microbial community diversity and carbon source utilization - Wenjie Zhang; Jinhua Wang; Lusheng Zhu; Jun Wang; Shushuai Mao; Xiaojing Yan; Shengfang Wen; Lanjun Wang; Zikun Dong; Young Mo Kim (Environmental Geochemistry and Health, 2023)

Occurrence, distribution and potential risk to infants of neonicotinoids in breast milk: A case study in Hangzhou, China - Quan Zhang; Xunjie Mo; Jianlin Lou; Zeteng Ying; Yan Wang; Wei Dai (Science of The Total Environment, 2023)

Rice genotypes and root-associated niches shifted bacterial community in response to pollution of di-(2-ethylhexyl) phthalate (DEHP) for promoting DEHP removal - Cui-Lan Zhu; Hui-Xiong Lü; Yu-Hong Huang; Ji-liang Cheng; Hui Li; Yan-Wen Li; Ce-Hui Mo; Hai-Ming Zhao; Lei Xiang; Quan-Ying Cai (Journal of Hazardous Materials, 2023)

Screening of Bacillus altitudinis D47 from TNT red water-contaminated soil for highly dinitrotoluene sulfonate efficient biodegradation - Kunlong Su; Yan Wang; Yuchen Liu; Meifeng Liu; Xiao Men; Haibo Zhang; Mo Xian; Zhenying Wu; Chunxiang Fu (Journal of Cleaner Production, 2023)

Implanting nitrogen-doped graphene quantum dots on porous ultrathin carbon nitride for efficient metal-free photocatalytic hydrogen evolution - Hanxiang Chen; Zhao Mo; Zeming Wang; Pengcheng Yan; Peipei Sun; Guanyu Wu; Jinyuan Zhang; Xianglin Zhu; Liang Wang; Hui Xu (Journal of Environmental Chemical Engineering, 2023)

Effects of biofilm and co-culture with Bacillus velezensis on the synthesis of esters in the strong flavor Baijiu - Xiangyong Zeng; Zhenni Mo; Jia Zheng; Chaoyang Wei; Yifeng Dai; Yan Yan; Shuyi Qiu (International Journal of Food Microbiology, 2023)

Chlorogenic acid alleviates oxidative damage in hepatocytes by regulating miR-199a-5p/GRP78 axis - Jiaxin Li; Hengju Ge; Yang Xu; Jiahong Xie; Naymul Karim; Fujie Yan; Jianling Mo; Wei Chen (Food Bioscience, 2023)

Ameliorative effect of Fructus Gardeniae against lipotoxicity associated hepatocytes injury through activating Nrf2 signaling pathway - Hengju Ge; Jiaxin Li; Yang Xu; Jiahong Xie; Naymul Karim; Fujie Yan; Jianling Mo; Wei Chen (Food Bioscience, 2023)

Curcumin alleviates lipid deposition in hepatocytes through miR-3666/AMPK axis regulation - Hengju Ge; Jiaxin Li; Yang Xu; Jiahong Xie; Naymul Karim; Fujie Yan; Jianling Mo; Wei Chen (Food Bioscience, 2023)

Achieving ultrahigh energy density and ultrahigh efficiency simultaneously via characteristic regulation of polar nanoregions - Leiyang Zhang; Mo Zhao; Yule Yang; Yang Li; Mingyang Tang; Dong Wang; Xiaoyong Wei; Gang Liu; Yan Yan; Li Jin (Chemical Engineering Journal, 2023)

Changes of spring wind erosion based on wind erosion climate factor in the black soil region of Northeast China - Ping Yan; Sheng-tai Ji; Xiu-fen Li; Hai-xia Zhu; Liang-liang Wang; Mo Zhai; Ping Wang; Hui-ying Zhao (Journal of Mountain Science, 2023)

Research on the policy effect and mechanism of green finance to reduce environmental pollution: micro evidence from 285 cities in China - Xuehui Yang; Mo Wei; Yan Li; Yiming Jiang (Environmental Science and Pollution Research, 2023)

Polyethylene and polypropylene microplastics reduce chemisorption of cadmium in paddy soil and increase its bioaccessibility and bioavailability - Jing-Jie Guo; Fen Li; Hai-Chuan Xiao; Bai-Lin Liu; Lin-Nan Feng; Peng-Fei Yu; Can Meng; Hai-Ming Zhao; Nai-Xian Feng; Yan-Wen Li; Quan-Ying Cai; Lei Xiang; et al. (Journal of Hazardous Materials, 2023)

Endophytic Phthalate-degrading Bacillus subtilis N-1-gfp colonizing in soil-crop system shifted indigenous bacterial community to remove di-n-butyl phthalate - Li-Hui Liu; Jia-Yan Zhang; Guang-Xuan Tang; Yu-Hong Huang; Xiang-Qing Xie; Jun Geng; Hui-Xiong Lü; Hui Li; Yan-Wen Li; Ce-Hui Mo; Hai-Ming Zhao; Quan-Ying Cai (Journal of Hazardous Materials, 2023)

Effect of sulfamethazine on the horizontal transfer of plasmid-mediated antibiotic resistance genes and its mechanism of action - Xiaojing Yan; Wenwen Liu; Shengfang Wen; Lanjun Wang; Lusheng Zhu; Jun Wang; Young Mo Kim; Jinhua Wang (Journal of Environmental Sciences, 2023)

Modelling and implementation of an in-situ thermally regenerated adsorption module for removing gaseous xylene - Xiao Lei; Qiwei Chen; Yan Wang; Jinhan Mo (Building and Environment, 2023)

Prehistoric damaging earthquake promoted the decline of “Heluo Ancient State” in Early China - Xiu Hu; Peng Lu; Youli Li; Duowen Mo; Wanfa Gu; Qingri Liu; Ailun Guo; Panpan Chen; Hui Wang; Yan Tian; Xu Wang; Yayi Hu; et al. (Science China Earth Sciences, 2023)

Development of QuEChERS coupled with UHPLC–MS/MS for simultaneous determination of eight neonicotinoid pesticides in breast milk - Zeteng Ying; Lili Fu; Sijia Gu; Yan Wang; Xunjie Mo; Tao Tang; Hangbiao Jin; Quan Zhang (Environmental Monitoring and Assessment, 2023)

Multidimensional identification of single and regional meteorological drought considering flash‐season synthesis employed daily standardized effective precipitation and drought index in Guangxi, China - Yang Yun‐chuan; Yang Jia‐zhen; Tian Yi; Liao Li‐ping; Gan Ru‐min; Wang Wei‐quan; Wang Ting‐yan; Mo Chong‐xun; Li Xun‐gui; Sun Gui‐kai (International Journal of Climatology, 2023)
The frequent occurrence of extreme drought events in Guangxi has caused huge losses to human beings and economy in the region for many years. Therefore, this study adopted run theory and the objective identification method of regional extreme events (OITREE) and then carried out the comprehensive feature identification of multidimensional elements such as intensity, duration and area of meteorological drought events based on the daily standardized effective precipitation and drought index (SWAP) sequence of Guangxi from 1979 to 2018a. By comparing the evolutionary characteristics of drought elements identified by grid SWAP statistical analysis and OITREE, an integrated optimization scheme combining the accuracy of grid analysis and area identification is formed in this study. It was confirmed that the above two analysis methods had good correlation and consistency in revealing the evolution process of multidimensional elements of drought events. In terms of the frequency of drought events over a long period of time and the comprehensive characteristics of each element, the identification results of the OITREE method can better reveal the comprehensive characteristics of drought in Guangxi. Furthermore, the study found that flash droughts and seasonal droughts occurred alternately and were superimposed concurrently in Guangxi, and there were significant differences in the multidimensional spatial and temporal characteristics of these two types of droughts. Specifically, the frequency of flash drought was 1.60–4.00 times·(a) −1 , the duration varied from 20 to 60 days·(a) −1 and the concentration point of drought had a region‐wide dispersion; while the frequency of seasonal drought was 0.82–1.65 times·(a) −1 , the duration varied from 40–105 days·(a) −1 and the concentration point of drought had a local concentration. The research results can provide effective scientific support for operational drought refined forecast and early warning, and smart regulation of drought disaster risk.

Model for predicting the hydraulic elements of drip irrigation system with automatic flushing valves under high sediment water - Hao Gao; Yan Mo; Jiandong Wang; Feng Wu; Ni Gao; Shihong Gong (Biosystems Engineering, 2023)

Chemical speciation determines combined cytotoxicity: Examples of biochar and arsenic/chromium - Jian Liu; Yuting Wen; Yucong Mo; Weizhen Liu; Xiliang Yan; Hongyu Zhou; Bing Yan (Journal of Hazardous Materials, 2023)

A comprehensive assessment of runoff dynamics in response to climate change and human activities in a typical karst watershed, southwest China - Chongxun Mo; Shufeng Lai; Qing Yang; Keke Huang; Xingbi Lei; Lufeng Yang; Zhiwei Yan; Changhao Jiang (Journal of Environmental Management, 2023)

Three coordinate nitrogen (N3c) vacancies from in-situ hydrogen bond breaking over polymeric carbon nitride for efficient photocatalysis - Jiajun Fu; Zhao Mo; Hanxiang Chen; Zhigang Chen; Xianglin Zhu; Jia Yan; Jinyuan Liu; Yuechang Wei; Huaming Li; Hui Xu (Journal of Environmental Chemical Engineering, 2023)

Glycoside hydrolase family 5 gene Pp07886 in Pythium porphyrae: Identification, characterization, expression pattern, and activation of the host immunity - Huichao Yang; Peiwen Weng; Zaiduo Liu; Yongwei Yan; Lei Tang; Jie Li; Yunxiang Mao; Zhaolan Mo (Algal Research, 2023)

Late Quaternary slip rate of the Fengmenkou-Wuzhiling fault at the southern margin of North China block (S-NCB) - Xiu Hu; Youli Li; Peizhen Zhang; Quanxing Luo; Peng Lu; Duowen Mo; Yipeng Zhang; Qingri Liu; Ailun Guo; Yan Tian; Zhen Wang (Tectonophysics, 2023)

Genome mining-guided activation of two silenced tandem genes in Raoultella ornithinolytica XF201 for complete biodegradation of phthalate acid esters - Nai-Xian Feng; Fei Zhang; Yunchang Xie; Hui Bin; Lei Xiang; Yan-Wen Li; Fantao Zhang; Yunhong Huang; Hai-Ming Zhao; Quan-Ying Cai; Ce-Hui Mo; Qing X. Li (Science of The Total Environment, 2023)

Coupling effects of nitrate reduction and sulfur oxidation in a subtropical marine mangrove ecosystem with Spartina alterniflora invasion - Shiqing Nie; Shuming Mo; Tingwei Gao; Bing Yan; Peihong Shen; Muhammad Kashif; Zufan Zhang; Jinhui Li; Chengjian Jiang (Science of The Total Environment, 2023)

Feasibility evaluation of novel anionic-nonionic gemini surfactants for surfactant-enhanced aquifer remediation - Xue Liang; Yan Li; Jing Bai; Jun Dong; Wende Li; Yanyang Mo; Dihan Jiang; Weihong Zhang (Journal of Cleaner Production, 2023)

Potential of metal-organic frameworks to adsorb ethylene for fresh produce active packaging applications - Yan Zhang; Shuo Yuan; Xi Chen; Mo Chen; Bingxin Sun; Dowan Kim; Kit Yam (Food Packaging and Shelf Life, 2023)

Modulation of Antioxidant Attributes and Grain Yield in Fragrant Rice by Exogenous Cu Application - Siren Cheng; Zhenming Fang; Xianchao Cheng; Yizhu Wu; Lifang Mo; Chongyang Yan; Langshan Zhou; Yong Ren (Journal of Plant Growth Regulation, 2023)

A novel protein domain is important for photosystem II complex assembly and photoautotrophic growth in angiosperms - Wei Li; Jiangfan Guo; Xue Han; Xiaowen Da; Kai Wang; Hongfei Zhao; Shi-Tang Huang; Bosheng Li; Hang He; Ruirui Jiang; Shichen Zhou; Peng Yan; et al. (Molecular Plant, 2023)

Response of partial nitritation/anammox granules to biodegradable organic input in bacterial community and functions - Feiyue Qian; Yaru Liu; Chenyun Mo; Huan Zhang; Feng Yan; Junjun Gao; Jinlong Zhuang (Journal of Water Process Engineering, 2023)

Thiram-induced hyperglycemia causes tibial dyschondroplasia by triggering aberrant ECM remodeling via the gut-pancreas axis in broiler chickens - Quan Mo; Muhammad Fakhar-e-Alam Kulyar; Chuxian Quan; Yanmei Ding; Yan Zhang; Lihong Zhang; Huachun Pan; Jiakui Li (Journal of Hazardous Materials, 2023)

Adaptation of bacterial community in maize rhizosphere for enhancing dissipation of phthalic acid esters in agricultural soil - Yu-Hong Huang; Yu-Jie Yang; Xiaolian Wu; Cui-Lan Zhu; Huixiong Lü; Hai-Ming Zhao; Lei Xiang; Hui Li; Ce-Hui Mo; Yan-Wen Li; Quan-Ying Cai; Qing X. Li (Journal of Hazardous Materials, 2023)

Iron-rich digestate biochar toward sustainable peroxymonosulfate activation for efficient anaerobic digestate dewaterability - Zhihua Mo; Zexing Tan; Jialin Liang; Lei Zhang; Chengjian Li; Shaosong Huang; Shuiyu Sun; Yan Sun (Journal of Hazardous Materials, 2023)

Metabolomic profiles in a green alga (Raphidocelis subcapitata) following erythromycin treatment: ABC transporters and energy metabolism - Jiezhang Mo; Zhihua Ma; Shiwei Yan; Napo KM Cheung; Fangshe Yang; Xiunan Yao; Jiahua Guo (Journal of Environmental Sciences, 2023)

Evaluation of reference genes for quantitative real-time PCR normalization in the Neopyropia (Pyropia) oomycete pathogen Pythium porphyrae - Huichao Yang; Yongwei Yan; Peiwen Weng; Congcong Sun; Jiaxing Yu; Lei Tang; Jie Li; Zhaolan Mo (Journal of Applied Phycology, 2023)

Divergence of epibacterial community assemblage correlates with malformation disease severity in Saccharina japonica seedlings - Yongwei Yan; Shanshan Wang; Kuimei Liu; Zhaolan Mo; Huichao Yang; Xiaojun Rong; Jie Li (Frontiers in Marine Science, 2023)
Malformation disease (MD) is one of the major constraints in the mariculture of the commercially important seaweed Saccharina japonica , which can cause severe losses of the kelp seedlings in the production process. However, the pathogenesis of MD remains largely undetermined. In this study, using cultivation experiments under laboratory conditions, MD severity was estimated for the young sporophytes of S. japonica , which were separately cultivated under different treatment conditions, including light intensity, duration of light exposure, and maturity level of the parent kelp. The associations between MD severity and epibacterial community divergence and assembly patterns were characterized. Higher MD severity significantly correlated with longer light exposure, and with both unmatured and overmatured parent kelp. The bacterial classes γ-Proteobacteria and α-Proteobacteria dominated all samples, but different MD severities were associated with different epibacterial communities. Comparisons of predicted functions for epibacterial communities revealed that longer light exposure led to a depletion in development and regeneration, while overmatured parent kelp resulted in a depletion in glycan biosynthesis and metabolism. Functional comparisons of the epibacterial communities between normal and unmatured parent kelp-generated seedlings revealed significantly different categories related to metabolism, environmental information processing, cellular processes, drug resistance, and bacterial infection. The significantly different pathways between groups, notably those related to bacterial infection and cellular processes, were partly consistent with the differences in bacterial compositions. The assembly of epiphytic bacterial communities was predominately governed by deterministic processes, and less impact was determined when there was significantly higher MD severity except when using overmatured parent kelp. Co-occurrence networks of the epibacterial communities associated with higher MD severity contained fewer nodes and exhibited lower modularity, but had higher graph density and degrees compared with those of seedlings with lower MD severity, indicating more complicated interactions. Nesterenkonia , Glycocaulis , Halomonas , Pseudoalteromonas , Pseudomonas , Loktanella , and Cobetia were frequently determined keystone taxa in communities associated with higher MD severity. The present study enhances our understanding of the factors significantly associated with MD severity and the potential roles of epimicrobiome in determining the disease severity, which will be useful for disease management in the future.

Revealing microcystin-LR ecotoxicity to earthworm (Eisenia fetida) at the intestinal cell level - Xiang Liu; Jin-Cheng Ye; Fen Li; Rong-Jun Gao; Xiao-Xiao Wang; Ji-Liang Cheng; Bai-Lin Liu; Lei Xiang; Yan-Wen Li; Quan-Ying Cai; Hai-Ming Zhao; Ce-Hui Mo; et al. (Chemosphere, 2023)

A novel method based on solid phase extraction and liquid chromatography-tandem mass spectrometry warrants occurrence of trace xanthates in water - Yu-Ting Qiao; Ying-Xin Lu; Peng-Fei Yu; Nai-Xian Feng; Yan-Wen Li; Hai-Ming Zhao; Quan-Ying Cai; Lei Xiang; Ce-Hui Mo; Qing X. Li (Chemosphere, 2023)

Spread and driving factors of antibiotic resistance genes in soil-plant system in long-term manured greenhouse under lead (Pb) stress - Lanjun Wang; Xiaojing Yan; Lusheng Zhu; Jun Wang; Baoshan Xing; Young Mo Kim; Jinhua Wang (Science of The Total Environment, 2023)

Potential impact of industrial transfer on PM2.5 and economic development under scenarios oriented by different objectives in Guangdong, China - Haihua Mo; Yingchang You; Liping Wu; Fenghua Yan; Ming Chang; Weiwen Wang; Peng Wang; Xuemei Wang (Environmental Pollution, 2023)

Corrigendum to “Rapid start-up and stable operation of an aerobic/oxic/anoxic simultaneous nitrification, denitrification, and phosphorus removal reactor with no sludge discharge” [Bioresour. Technol. 362 (2022) 127777] - Qiulai He; Xiaohui Yan; Zhidong Fu; Yihang Zhang; Peng Bi; Xingliang Mo; Peng Xu; Jingwei Ma (Bioresource Technology, 2023)

Circular RNA circCCNB1 inhibits the migration and invasion of nasopharyngeal carcinoma through binding and stabilizing TJP1 mRNA - Mengyao Zhao; Yian Wang; Fenghua Tan; Lingyun Liu; Xiangchan Hou; Chunmei Fan; Le Tang; Yongzhen Mo; Yumin Wang; Qijia Yan; Zhaojian Gong; Zheng Li; et al. (Science China Life Sciences, 2022)

Regional water pollution management pathways and effects under strengthened policy constraints: the case of Tianjin, China - Yujia Wang; Mo Zhang; Chonggang Yang; Yan He; Meiting Ju (Environmental Science and Pollution Research, 2022)

Ectopic Expression of Erigeron breviscapus JAZ1 Affects JA-Induced Development Processes in Transgenic Arabidopsis - Mo Chen; Wei Zhang; Mi Yan; Simei He; Yingchun Lu; Guanghui Zhang; Bing Hao; Wei Fan; Yanru Hu; Shengchao Yang (Plant Molecular Biology Reporter, 2022)

Numerical study of storm surge-induced coastal inundation in Laizhou Bay, China - Zhao Li; Shuiqing Li; Po Hu; Dongxue Mo; Jian Li; Mei Du; Jie Yan; Yijun Hou; Baoshu Yin (Frontiers in Marine Science, 2022)
Storm surge inundation can induce great disasters in coastal regions, and Laizhou Bay (LZB), located in the Bohai Sea, is a bay that frequently experiences coastal storm flooding. In this study, we perform a numerical study of the effects of wind and waves on the storm surge-induced coastal inundation in the LZB using the coupled model ADCIRC+SWAN. Two historical typhoons (No. 9216 Typhoon Polly (TY9216) and No. 1909 Typhoon Lekima (TY1909)) are considered, wave effects in terms of wind-wave-induced surface stress and radiation stress are included, and two widely used wind data sources (CFS and ERA5) are used. The results indicate that the total inundation area and average inundation depth in the LZB during TY1909 are 10.70%-19.16% larger than during TY9216, and the CFS wind field reproduces a 14.31%-23.05% more intense inundation simulation than does the ERA5 wind field. The wave-induced surface stress plays the primary role in increasing the inundation area and average depth by up to 11.42%-18.50% and 5.82%-8.75%, respectively, and the wave-induced radiation stress also increases the inundation area and average depth by 3.80%-6.60% and 3.70%-4.57%, respectively. The results highlight the importance of considering wave effects in storm surge-induced coastal inundation simulations, and we demonstrate that the wave effects on the inundation area can be quite sensitive to the choice of wind field source.

Regulation of OsLPR1 gene on the formation of rice root iron plaque under low phosphorus - Yan Ding; Menglian Ren; Shuangrong Mo; Jing Liu; Zegang Wang; Cailin Ge; Yulong Wang (Plant Biotechnology Reports, 2022)

Alterations in Epiphytic Bacterial Communities during the Occurrence of Green Rot Disease in Saccharina japonica Seedlings - Yongwei Yan; Shanshan Wang; Jie Li; Fuli Liu; Zhaolan Mo (Journal of Marine Science and Engineering, 2022)
Bacteria are one of the causes of green rot disease (GRD) in Saccharina japonica mariculture, which may lead to complete failure of seedling production. However, the association between bacterial community and host disease severity remains largely unknown. Therefore, in this study, the bacterial communities associated with GRD-infected seedlings with naturally varying disease severity from two seedling hatcheries in Northern China were analyzed to investigate the interactions between bacterial communities and GRD. The results indicated incorrect nutrient supply in both sites. Gammaproteobacteria, Alphaproteobacteria, and Bacteroidetes were prevalent in all samples. Significant structural alterations were detected for epibacterial communities, which were further evidenced by differently abundant bacterial taxa associated with seedlings with varying disease severity. The predicted pathways of bacterial adhesion and antimicrobial compounds biosynthesis were significantly enriched in less severely diseased seedlings, whereas glutathione metabolism and lipopolysaccharide biosynthesis were significantly increased in more severely diseased seedlings. The predicted categories of a two-component system, flagellar assembly, bacterial chemotaxis, and biofilm formation were significantly enriched in the bacterioplankton in more severely infected seawater. The differential bacterial community compositions and predicted functions provide new clues to elucidate the mechanism underlying the interaction between GRD occurrence and bacterial communities.

Dynamics of Planktonic Microbial Community Associated with Saccharina japonica Seedling - Shanshan Wang; Yongwei Yan; Hao Qian; Jie Li; Tao Liu; Zhaolan Mo (Journal of Marine Science and Engineering, 2022)
Macroalgae interact with planktonic microbes in seawater. It remains unclear how planktonic microbes interact with the environment and each other during the cultivation processes of commercially important algal species. Such an interaction is important for developing environment-friendly mariculture methods. In this study, the dynamics of the planktonic microbial community associated with Saccharina japonica were profiled during the seedling production stage, with its environmental correlation and co-occurrence pattern determined simultaneously. Microbial richness increased and positively correlated with light intensity and contents of NO3− and PO43−. A clear temporal succession of the community was observed, which coincided with changes in light intensity, dissolved oxygen, pH, and NO3− content. α-Proteobacteria, Bacteroidetes, γ-Proteobacteria, and the genera prevalent in these taxa dominated the planktonic microbial community, and their relative abundance temporally changed. A profile of keystone taxa that is different from prevalent genera was identified based on betweenness centrality scores. A modularized co-occurrence pattern was determined, in addition to intensified species-to-species interactions at the core of the co-occurrence network. These findings expanded our cognization of the planktonic microbial community in response to S. japonica cultivation.

The Spinal-Parabrachial-Mesencephalic Circuit: A Possible Explanation of How Pain Leads to Emotional Disorders - Hongze Yan; Guokang Mo; Ngoc T. Ha; Juan Deng (Neuroscience Bulletin, 2022)

Molecular and functional characterization of the retinol-binding protein 4 (RBP4) in hepatocytes of Schizothorax prenanti in response to palmitic acid - Yan Wang; Peng Zhu; Jiahui Ni; Qilang Mo; Wei Luo; Zongjun Du; Jun Jiang; Song Yang; Liulan Zhao; Quan Gong (Fish Physiology and Biochemistry, 2022)

Investigation of factors influencing the release of chloropropanols (3-MCPD and 1,3-DCP) from food contact paper - Huai-ning Zhong; Ying Zeng; Dao-yuan Yang; Ze-chun Wu; Dan Li; Hai-xia Sui; Jie Gao; Yan-fen Chen; Ce-Hui Mo (Food Additives & Contaminants: Part A, 2021)

A new glucopyranoside from the leaves of Microsorium fortunei - Mengqi Yan; Qin Luo; Xianli Zhou; Qinghu Mo; Caifeng Peng; Xiaoya Xian; Xiao Huang; Xinping Yang; Xu Chen; Chengqin Liang (Natural Product Research, 2021)

Cytochalasins from endophytic Diaporthe sp. GDG-118 - Xishan Huang; Dexiong Zhou; Yan Liang; Xiaobo Liu; Fei Cao; Yuyue Qin; Tuxiang Mo; Zhaolong Xu; Jun Li; Ruiyun Yang (Natural Product Research, 2021)

Mechanism of Low Phosphorus Inducing the Main Root Lengthening of Rice - Yan Ding; Zegang Wang; Shuangrong Mo; Jing Liu; Yuan Xing; Yuanping Wang; Cailin Ge; Yulong Wang (Journal of Plant Growth Regulation, 2021)

Drought tolerance in high-generation transgenic maize inbred lines overexpressing the betaine aldehyde dehydrogenase gene - He Zhao; Qi Zhang; Mo Zhang; Yu-Kun Jin; Zhen-Zhong Jiang; Nan Jiang; Qi Wang; Jing Qu; Shu-Yan Guan; Pi-Wu Wang (Cereal Research Communications, 2021)

Mitogen-activated protein kinase action in plant response to high-temperature stress: a mini review - Shuangrong Mo; Ying Qian; Wenjuan Zhang; Lu Qian; Yan Wang; Ge Cailin; Haidong Ding (Protoplasma, 2021)

Construction of an infectious full-length cDNA clone of potato aucuba mosaic virus - Buyang Chen; Qi Lin; Yueyan Yin; Liangliang Jiang; Fang Wang; Shuzhen Hu; Xinyang Wu; Fei Xu; Jiejun Peng; Hongying Zheng; Chengqi Yan; Xiaohan Mo; et al. (Archives of Virology, 2021)

MicroRNA-125b alleviates hydrogen-peroxide-induced abnormal mitochondrial dynamics in HT22 cells by inhibiting p53 - Yan Huang; Songyun Deng; Yuhang Ai; Yunan Mo; Wenchao Li; Qianyi Peng; Li Huang; Lina Zhang (Metabolic Brain Disease, 2021)

Retraction Note to: Resibufogenin suppresses tumor growth and inhibits glycolysis in ovarian cancer by modulating PIM1 - Qian Li; Chuanwu Jiang; Yan Wang; Minghua Wei; Huijin Zheng; Yanqi Xu; Xuegang Xu; Fengyu Jia; Kai Liu; Gang Sun; Jianhua Zang; Ping Mo (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)

Evaluation of subsurface, mulched and non-mulched surface drip irrigation for maize production and economic benefits in northeast China - Dan Wang; Guangyong Li; Yan Mo; Ding Zhang; Xinhan Xu; Carol Jo Wilkerson; Gerrit Hoogenboom (Irrigation Science, 2021)

High-Level Expression and Purification of Melittin in Escherichia coli Using SUMO Fusion Partner - Qiu-chi Chen; Lei Liu; Tian-Yi Yu; Lu Tang; Mo-li Yin; Wen-he Zhu; Xiu-yun Jiang; Hui-yan Wang (International Journal of Peptide Research and Therapeutics, 2021)

Efficient and Economical Allocation of Irrigation Water under a Changing Environment: a Stochastic Multi‐Objective Nonlinear Programming Model* - Zehao Yan; Mo Li; Zhong Li (Irrigation and Drainage, 2021)
Water scarcity causes conflicts between natural resources and socio‐economic development which reinforces the need for optimal allocation of irrigation water resources. Irrigation water resource allocation is a complex problem due to various uncertainties in natural conditions. In this study, a stochastic multi‐objective nonlinear programming model is developed for irrigation water allocation under uncertainty. The model is capable of balancing the conflicting objectives of maximizing both net economic benefit (NEB) and irrigation water use efficiency (IWUE). Moreover, it can reflect the random nature of water availability, and provide alternative water allocation schemes in response to climate change. The applicability of the developed model is demonstrated by a case study in north‐west China. Trade‐offs between NEB and IWUE are presented. Irrigation water allocation schemes to cope with changing environments, including climate change and varying water availability, are also proposed. The results demonstrate that the developed model can generate solutions that save irrigation water while ensuring NEB. This model is a useful tool to support the formulation of optimized water resources management policies in a changing environment.

Use of biochar as feed supplements for animal farming - Ka Yan Man; Ka Lai Chow; Yu Bon Man; Wing Yin Mo; Ming Hung Wong (Critical Reviews in Environmental Science and Technology, 2021)

Optimization of agricultural water–food–energy nexus in a random environment: an integrated modelling approach - Mo Li; Vijay P. Singh; Qiang Fu; Dong Liu; Tianxiao Li; Yan Zhou (Stochastic Environmental Research and Risk Assessment, 2021)

Nitrogen Regulates the Grain Yield, Antioxidant Attributes, and Nitrogen Metabolism in Fragrant Rice Grown Under Lead-Contaminated Soil - Huoyi Feng; Yuzhan Li; Yangfan Yan; Xinhang Wei; Yihan Yang; Long Zhang; Lin Ma; Wu Li; Xiangru Tang; Zhaowen Mo (Journal of Soil Science and Plant Nutrition, 2020)

Amitriptyline Reduces Sepsis-Induced Brain Damage Through TrkA Signaling Pathway - Lina Zhang; Xiaobei Peng; Yuhang Ai; Li Li; Shuangpin Zhao; Zhiyong Liu; Qianyi Peng; Songyun Deng; Yan Huang; Yunan Mo; Li Huang (Journal of Molecular Neuroscience, 2020)

Role of major histocompatibility complex II antigen‐presentation pathway genes in orange‐spotted grouper infected with Cryptocaryon irritans - Jun‐Jin Deng; Shun Xu; Yan‐Wei Li; Dong‐Dong Xu; Ze‐Quan Mo; Jia‐Zhou Li; Xue‐Ming Dan; Xiao‐Chun Luo (Journal of Fish Diseases, 2020)
Cryptocaryon irritans , a pathogen model for fish mucosal immunity, causes skin mucosal and systematic humoral immune response. Where and how MHC II antigen presentation occurs in fish infected with C . irritans remain unknown. In this study, the full‐length cDNA of the grouper cysteine protease CTSS was cloned. The expression distributions of six genes (CTSB, CTSL, CTSS, GILT, MHC IIA and MHC IIB) involved in MHC II antigen presentation pathway were tested. These genes were highly expressed in systematic immune tissues and skin and gill mucosal‐associated immune tissues. All six genes were upregulated in skin at most time points. Five genes expected CTSS was upregulated in spleen at most time points. CTSB, CTSL and MHC IIA were upregulated in the gill and head kidney at some time points. These results indicate that the presentation of MHC II antigen intensively occurred in local infected skin and gill. Spleen, not head kidney, had the most extensive systematic antigen presentation. In skin, six genes most likely peaked at day 2, earlier than in spleen (5–7 days), marking an earlier skin antibody peak than any recorded in serum previously. This significant and earlier mucosal antigen presentation indicates that specific immune response occurs in local mucosal tissues.

Arsenic trioxide alleviates acute graft-versus-host disease by modulating macrophage polarization - Xiao Liu; Yan Su; Xueyan Sun; Haixia Fu; Qiusha Huang; Qi Chen; Xiaodong Mo; Meng Lv; Yuan Kong; Lanping Xu; Xiaojun Huang; Xiaohui Zhang (Science China Life Sciences, 2020)

Fasudil attenuates glial cell-mediated neuroinflammation via ERK1/2 and AKT signaling pathways after optic nerve crush - Wei Huang; Qianqian Lan; Li Jiang; Wenya Yan; Fen Tang; Chaolan Shen; Hui Huang; Haibin Zhong; Jian Lv; Siming Zeng; Min Li; Zhongxiang Mo; et al. (Molecular Biology Reports, 2020)

Direct and indirect effects of microplastics on bivalves, with a focus on edible species: A mini-review - Feng Zhang; Yu Bon Man; Wing Yin Mo; Ka Yan Man; Ming Hung Wong (Critical Reviews in Environmental Science and Technology, 2020)

Silencing of Long Non-coding RNA GAS5 Suppresses Neuron Cell Apoptosis and Nerve Injury in Ischemic Stroke Through Inhibiting DNMT3B-Dependent MAP4K4 Methylation - Yiming Deng; Duanduan Chen; Feng Gao; Hong Lv; Guojun Zhang; Xuan Sun; Lian Liu; Dapeng Mo; Ning Ma; Ligang Song; Xiaochuan Huo; Tianyi Yan; et al. (Translational Stroke Research, 2020)

Effects of arbuscular mycorrhizal fungi on redox homeostasis of rice under Cd stress - Hui Li; Xun Wen Chen; Li Wu; Na Luo; Wei Xiong Huang; Ce Hui Mo; Yan Wen Li; Lei Xiang; Hai Ming Zhao; Quan Ying Cai; Ming Hung Wong (Plant and Soil, 2020)

Optimization of irrigation and fertilization of drip‐irrigated corn in the chernozem area of north‐east China based on the CERES‐Maize model - Chunxiao Fu; Jiandong Wang; Shihong Gong; Yanqun Zhang; Chuanjuan Wang; Yan Mo (Irrigation and Drainage, 2020)
To improve water and nitrogen utilization efficiency, and reduce nitrogen leaching in the chernozem area of north‐east China, field trial data and the CERES‐Maize model were used to optimize irrigation and fertilization management of drip‐irrigated corn. In this study field trial data for drip‐irrigated corn from 2014 and 2015 were used to calibrate and validate the CERES‐Maize model. Results show that yield and nitrogen leaching declined with decrease in the nitrogen fertilizer amount applied. Compared with the traditional nitrogen fertilizer amount applied in the study area (330 kg ha¯¹), yield was decreased with nitrogen fertilizer amounts of ≤170 kg ha¯¹, and nitrogen leaching was decreased with nitrogen fertilizer amounts of ≤240 kg ha¯¹. Yield was decreased in the absence of or reduced topdressing at the jointing stage, and nitrogen leaching was increased by topdressing at the jointing stage. Based on the results of simulations, it is suggested that drip‐irrigated corn in the chernozem area should be irrigated three or four times during the entire growth period. A total nitrogen fertilizer amount of 240 or 230 kg ha¯¹, and topdressing ratios at the jointing, tasseling and grain‐filling stages of 2/5–0‐3/5 or 1/3–1/3–1/3 were recommended. Eight optimal irrigation and fertilization schedules were identified. © 2020 John Wiley & Sons, Ltd.

Urban Geoheritage Sites Under Strong Anthropogenic Pressure: Example from the Chaohu Lake Region, Hefei, China - Weilun Kong; Yunhuai Li; Kongliang Li; Mo Chen; Yan Peng; Degao Wang; Lijun Chen (Geoheritage, 2020)

Genomic analyses of heat stress transcription factors (HSFs) in simulated drought stress response and storage root deterioration after harvest in cassava - Jian Zeng; Chunlai Wu; Cheng Wang; Fengfeng Liao; Jiajia Mo; Zehong Ding; Weiwei Tie; Yan Yan; Wei Hu (Molecular Biology Reports, 2020)

Genetic analysis and fine mapping of the gall midge resistance gene Gm5 in rice (Oryza sativa L.) - Hailian Zhou; Xinyi Wang; Yi Mo; Yang Li; Liuhui Yan; Zhihua Li; Wan Shu; Ling Cheng; Fengkuan Huang; Yongfu Qiu (Theoretical and Applied Genetics, 2020)

Anti-clogging performance optimization for dentiform labyrinth emitters - Bin Yang; Jiandong Wang; Yanqun Zhang; Haitao Wang; Xiaopeng Ma; Yan Mo (Irrigation Science, 2020)

ABA and sucrose co-regulate strawberry fruit ripening and show inhibition of glycolysis - Ya Luo; Cong Ge; Yajie Ling; Fan Mo; Min Yang; Leiyu Jiang; Qing Chen; Yuanxiu Lin; Bo Sun; Yong Zhang; Yan Wang; Mengyao Li; et al. (Molecular Genetics and Genomics, 2020)

Succession of bacterial community and methanotrophy during lake shrinkage - Yongliang Mo; Feng Jin; Yan Zheng; Taogetao Baoyin; Adrian Ho; Zhongjun Jia (Journal of Soils and Sediments, 2020)

Influence of the degree of donor bone marrow hyperplasia on patient clinical outcomes after allogeneic hematopoietic stem cell transplantation - Feifei Tang; Xiaodong Mo; Xiaohui Zhang; Yu Wang; Chenhua Yan; Yuhong Chen; Huan Chen; Wei Han; Yao Chen; Fengrong Wang; Jingzhi Wang; Yuqian Sun; et al. (Science China Life Sciences, 2020)

Mechanism of CNP-mediated DG-PKC and IP4 signaling pathway in diabetic rats with gastric motility disorder - Hui-Ming Lian; Jun-Yu Guo; Yan Sun; Mo-Han Zhang; Li-Hua Piao; Zheng Jin; Ying-Lan Cai (Molecular Biology Reports, 2020)

Development of a PCR method for detection of Pseudoalteromonas marina associated with green spot disease in Pyropia yezoensis - Huichao Yang; Yongwei Yan; Jie Li; Lei Tang; Yunxiang Mao; Zhaolan Mo (Journal of Oceanology and Limnology, 2020)

Sorting nexins, a component of retromer complex, interact with SRK in Brassica oleracea - Jing Zeng; Xiaoping Lian; Yan-ling Mo; Jingjing Chen; Yihua Liu; Liang Zhao; Liquan Zhu (Acta Physiologiae Plantarum, 2020)

RETRACTED ARTICLE: Resibufogenin suppresses tumor growth and inhibits glycolysis in ovarian cancer by modulating PIM1 - Qian Li; Chuanwu Jiang; Yan Wang; Minghua Wei; Huijin Zheng; Yanqi Xu; Xuegang Xu; Fengyu Jia; Kai Liu; Gang Sun; Jianhua Zang; Ping Mo (Naunyn-Schmiedeberg's Archives of Pharmacology, 2019)

MicroRNA-365 Knockdown Prevents Ischemic Neuronal Injury by Activating Oxidation Resistance 1-Mediated Antioxidant Signals - Jia-Lin Mo; Zhi-Guang Pan; Xiao Chen; Yu Lei; Ling-Ling Lv; Cheng Qian; Feng-Yan Sun (Neuroscience Bulletin, 2019)

Occurrence and formation of halobenzoquinones in indoor and outdoor swimming pool waters of Nanning City, Southwest China - Huan Wu; Kunling Long; Du Lu; Yan Mo; Qiyuan Yang; Xiao Wei (Environmental Science and Pollution Research, 2019)

Joint toxicity of six common heavy metals to Chlorella pyrenoidosa - Ling-Yun Mo; Dan-Na Zhao; Meng Qin; Li-Tang Qin; Hong-Hu Zeng; Yan-Peng Liang (Environmental Science and Pollution Research, 2019)

Inventory Theory-Based Stochastic Optimization for Reservoir Water Allocation - Yaowen Xu; Qiang Fu; Yan Zhou; Mo Li; Yi Ji; Tianxiao Li (Water Resources Management, 2019)

Pathogenicity of an FAdV-4 isolate to chickens and its genomic analysis - Kai-kun Mo; Chen-fei Lyu; Shang-shang Cao; Xia Li; Gang Xing; Yan Yan; Xiao-juan Zheng; Min Liao; Ji-yong Zhou (Journal of Zhejiang University-SCIENCE B, 2019)

Individual differences in inhibitory control abilities modulate the functional neuroplasticity of inhibitory control - Mo Chen; Yan Jing Wu; Junjie Wu; Yongben Fu; Shuhua Li; Huanhuan Liu; Chunming Lu; Taomei Guo (Brain Structure and Function, 2019)

Involvement of glutamate receptors in regulating calcium influx in rice seedlings under Cr exposure - Yan-Hong Li; Xiao-Zhang Yu; Ling-Yun Mo; Yu-Juan Lin; Qing Zhang (Ecotoxicology, 2019)

The Inhibitory Effects of Nitrogen Deposition on Asymbiotic Nitrogen Fixation are Divergent Between a Tropical and a Temperate Forest - Mianhai Zheng; Wei Zhang; Yiqi Luo; Shiqiang Wan; Shenglei Fu; Senhao Wang; Nan Liu; Qing Ye; Junhua Yan; Bi Zou; Chengliang Fang; Yuxi Ju; et al. (Ecosystems, 2019)

Predicting the cytotoxicity of disinfection by-products to Chinese hamster ovary by using linear quantitative structure–activity relationship models - Li-Tang Qin; Xin Zhang; Yu-Han Chen; Ling-Yun Mo; Hong-Hu Zeng; Yan-Peng Liang; Hua Lin; Dun-Qiu Wang (Environmental Science and Pollution Research, 2019)

Quantitative Vulnerability Model of Earth Dam Overtopping and its Application - Chong-Xun Mo; Gui-Yan Mo; Liu Peng; Qing Yang; Xin-Rong Zhu; Qing-Ling Jiang; Ju-Liang Jin (Water Resources Management, 2019)

Detection of lncRNA-mRNA interaction modules by integrating eQTL with weighted gene co-expression network analysis - Xing-Bo Mo; Long-Fei Wu; Xin Lu; Xiao-Wei Zhu; Wei Xia; Lan Wang; Pei He; Peng-Fei Bing; Yong-Hong Zhang; Fei-Yan Deng; Shu-Feng Lei (Functional & Integrative Genomics, 2019)

Contribution of Cathepsin L to Autolysis of Sea Cucumber Stichopus japonicus Intestines - Jia-Nan Yan; Xiao-Kun Guo; Yue Tang; Ao-Ting Li; Zhi-Mo Zhu; Xiao-Qian Chai; Xiu-Hong Duan; Hai-Tao Wu (Journal of Aquatic Food Product Technology, 2019)

Induction and identification of tetraploid Hedychium coronarium through thin cell layer culture - Hong-Yan Tu; Ai-Ling Zhang; Wang Xiao; Ya-Rou Lin; Jun-Hui Shi; Yong-Wei Wu; Si-Tong Wu; Chun-Hui Zhong; Shui-Xiu Mo (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

Molecular analysis and serological survey of Tembusu virus infection in Zhejiang, China, 2010-2016 - Xiaozhi Huang; Huibo Qiu; Xing Peng; Wenbin Zhao; Xinhao Lu; Kaikun Mo; Yan Yan; Min Liao; Jiyong Zhou (Archives of Virology, 2018)

Indexing the relationship between polar motion and water mass change in a giant river basin - Suxia Liu; Shanshan Deng; Xingguo Mo; Haoming Yan (Science China Earth Sciences, 2018)

Cell culture establishment and regulation of two phenylethanoid glycosides accumulation in cell suspension culture of desert plant Cistanche tubulosa - Xiao Liu; Yaru Yan; Yuyu Liu; Ting Mo; Xiaohui Wang; Yuelin Song; Qingliang Chen; Yunfang Zhao; Shepo Shi; Pengfei Tu (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

Variation in accumulation, transport, and distribution of phthalic acid esters (PAEs) in soil columns grown with low- and high-PAE accumulating rice cultivars - Yang Wu; Xue-Xue Chen; Ting-Kai Zhu; Xing Li; Xiao-Hong Chen; Ce-Hui Mo; Yan-Wen Li; Quan-Ying Cai; Ming-Hung Wong (Environmental Science and Pollution Research, 2018)

Effects of Oxalic Acid on Arsenic Uptake and the Physiological Responses of Hydrilla verticillata Exposed to Different Forms of Arsenic - Wen Zheng; Zheng-yan Zhong; Hong-bin Wang; Hai-juan Wang; Dong-mo Wu (Bulletin of Environmental Contamination and Toxicology, 2018)

The distribution and functional relevance analysis of runs of homozygosity (ROHs) in Chinese Han female population - Yi-Hua Lu; Bing-Hua Wang; Wei Xia; Xing-Bo Mo; Long-Fei Wu; Xiao-Wei Zhu; Pei He; Fang-Fei Xie; Xin Lu; Fei-Yan Deng; Shu-Feng Lei (Molecular Genetics and Genomics, 2018)

Correlation analyses revealed global microRNA–mRNA expression associations in human peripheral blood mononuclear cells - Lan Wang; Jiang Zhu; Fei-Yan Deng; Long-Fei Wu; Xing-Bo Mo; Xiao-Wei Zhu; Wei Xia; Fang-Fei Xie; Pei He; Peng-Fei Bing; Ying-Hua Qiu; Xiang Lin; et al. (Molecular Genetics and Genomics, 2018)

Multiple correlation analyses revealed complex relationship between DNA methylation and mRNA expression in human peripheral blood mononuclear cells - Fang-Fei Xie; Fei-Yan Deng; Long-Fei Wu; Xing-Bo Mo; Hong Zhu; Jian Wu; Yu-Fan Guo; Ke-Qin Zeng; Ming-Jun Wang; Xiao-Wei Zhu; Wei Xia; Lan Wang; et al. (Functional & Integrative Genomics, 2018)

Toxicological effects of microcystin-LR on earthworm (Eisenia fetida) in soil - Hong-Fei Wen; Yan-Wen Li; Lei Xiang; Hai-Ming Zhao; Lei Chen; Quan-Ying Cai; Hui Li; Ce-Hui Mo; Dong-Mei Zhou; Ming-Hung Wong (Biology and Fertility of Soils, 2017)

Lack of human cytomegalovirus expression in single cells from glioblastoma tumors and cell lines - Travis S. Johnson; Zachary B. Abrams; Xiaokui Mo; Yan Zhang; Kun Huang (Journal of NeuroVirology, 2017)

Kinetics of Antioxidant-Producing Maillard Reaction in the Mixture of Ribose and Sea Cucumber ( Stichopus japonicus ) Gut Hydrolysates - Jia-Run Han; Zhi-Mo Zhu; Hai-Tao Wu; Na Sun; Yue Tang; Cui-Ping Yu; Chen-Chen Zhao; Zheng-Yu Zhang; Ao-Ting Li; Jia-Nan Yan (Journal of Aquatic Food Product Technology, 2017)

Bacillus zanthoxyli sp. nov., a novel nematicidal bacterium isolated from Chinese red pepper (Zanthoxylum bungeanum Maxim) leaves in China - Ma Li; Cao Yong Hong; Wang Xiao Yan; Zheng Shuai Chao; Yang Cheng Gang; Duo Jin Ling; Zhou Xing Kui; Xi Jia Qin; Zhu Ming Liang; Mo Ming He (Antonie van Leeuwenhoek, 2017)

Enhanced dissipation of DEHP in soil and simultaneously reduced bioaccumulation of DEHP in vegetable using bioaugmentation with exogenous bacteria - Hai-Ming Zhao; Rui-Wen Hu; He-Biao Huang; Hong-Fei Wen; Huan Du; Yan-Wen Li; Hui Li; Quan-Ying Cai; Ce-Hui Mo; Jie-Sheng Liu; Ming-Hung Wong (Biology and Fertility of Soils, 2017)

Two-Stage Prediction on Effects of Mixtures Containing Phenolic Compounds and Heavy Metals on Vibrio qinghaiensis sp. Q67 - Ling-Yun Mo; Jie Liu; Li-Tang Qin; Hong-Hu Zeng; Yan-Peng Liang (Bulletin of Environmental Contamination and Toxicology, 2017)

Effects of Glycyrrhetinic Acid on GSH Synthesis Induced by Realgar in the Mouse Hippocampus: Involvement of System X AG - $$ X_{AG^{-}} $$ , System X C - $$ X_{C^{-}} $$ , MRP-1, and Nrf2 - Yan-lei Wang; Mo Chen; Tao-guang Huo; Ying-hua Zhang; Ying Fang; Cong Feng; Shou-yun Wang; Hong Jiang (Molecular Neurobiology, 2017)

ApoA-I/SR-BI modulates S1P/S1PR2-mediated inflammation through the PI3K/Akt signaling pathway in HUVECs - Kun Ren; Yan-Ju Lu; Zhong-Cheng Mo; Xing -Liu; Zhen-Li Tang; Yue Jiang; Xiao-Shan Peng; Li Li; Qing-Hai Zhang; Guang-Hui Yi (Journal of Physiology and Biochemistry, 2017)

The Research on the Relationship of RAGE, LRP-1, and Aβ Accumulation in the Hippocampus, Prefrontal Lobe, and Amygdala of STZ-Induced Diabetic Rats - Lou-Yan Ma; Yu-Lang Fei; Xiao-Ye Wang; Song-Di Wu; Jun-Hui Du; Mei Zhu; Long Jin; Ming Li; Hai-Long Li; Jia-Jia Zhai; Lu-Peng Ji; Ran-Ran Ma; et al. (Journal of Molecular Neuroscience, 2017)

Experimental Rock Stability Assessment Using the Frozen–Thawing Test - Yan Du; Mo-wen Xie; Yu-jing Jiang; Bo Li; Santos Chicas (Rock Mechanics and Rock Engineering, 2017)

Integrative multi-omics analysis revealed SNP-lncRNA-mRNA (SLM) networks in human peripheral blood mononuclear cells - Wei Xia; Xiao-Wei Zhu; Xin-Bo Mo; Long-Fei Wu; Jian Wu; Yu-Fan Guo; Ke-Qin Zeng; Ming-Jun Wang; Xiang Lin; Ying-Hua Qiu; Lan Wang; Pei He; et al. (Human Genetics, 2017)

Variation in accumulation and translocation of di-n-butyl phthalate (DBP) among rice (Oryza sativa L.) genotypes and selection of cultivars for low DBP exposure - Quan-Ying Cai; Pei-Yun Xiao; Hai-Ming Zhao; Huixiong Lü; Qiao-Yun Zeng; Yan-Wen Li; Hui Li; Lei Xiang; Ce-Hui Mo (Environmental Science and Pollution Research, 2017)

Sodium P-Aminosalicylic Acid Improved Manganese-Induced Learning and Memory Dysfunction via Restoring the Ultrastructural Alterations and γ-Aminobutyric Acid Metabolism Imbalance in the Basal Ganglia - Chao-Yan Ou; Yi-Ni Luo; Sheng-Nan He; Xiang-Fa Deng; Hai-Lan Luo; Zong-Xiang Yuan; Hao-Yang Meng; Yu-Huan Mo; Shao-Jun Li; Yue-Ming Jiang (Biological Trace Element Research, 2017)

A novel thymidine phosphorylase mutation in a Chinese MNGIE patient - Hui-Fang Wang; Juan Wang; Yan-Ling Wang; Jian-Jian Fan; Gui-Lin Mo; Feng-Yin Gong; Zhi-Ming Chai; Jin Zhang; Hua-Xing Meng; Chang-Xin Li; Jun-Hong Guo; Chuan-Qiang Pu (Acta Neurologica Belgica, 2017)

Predicting the Binding Affinity of ERβ Ligands Based on a Novel Variable Selection Method - Hong-Yan Liu; Fei Zhang; Li-Tang Qin; Zhong-Sheng Yi; Xiu-Li Wang; Ling-Yun Mo (Interdisciplinary Sciences: Computational Life Sciences, 2016)

Nitrogen-Fixing and Plant Growth-Promoting Ability of Two Endophytic Bacterial Strains Isolated from Sugarcane Stalks - Yong-Xiu Xing; Chun-Yan Wei; Yao Mo; Li-Tao Yang; Si-Liang Huang; Yang-Rui Li (Sugar Tech, 2016)

Occurrence and risk assessment of tetracycline antibiotics in soil from organic vegetable farms in a subtropical city, south China - Lei Xiang; Xiao-Lian Wu; Yuan-Neng Jiang; Qing-Yun Yan; Yan-Wen Li; Xian-Pei Huang; Quan-Ying Cai; Ce-Hui Mo (Environmental Science and Pollution Research, 2016)

Paraventricular Nucleus Infusion of Epigallocatechin-3-O-Gallate Improves Renovascular Hypertension - Qiu-Yue Yi; Jie Qi; Xiao-Jing Yu; Hong-Bao Li; Yan Zhang; Qing Su; Tao Shi; Dong-Mei Zhang; Jing Guo; Zhi-Peng Feng; Mo-Lin Wang; Guo-Qing Zhu; et al. (Cardiovascular Toxicology, 2016)

Root-lesion nematodes on maize in Shandong, China - Zhuo Qiu Qiu; Ai Su Mo; Qiong He; Hai Yan Wu; Xun Bo Zhou (Journal of General Plant Pathology, 2016)

Autoimmunity and dysmetabolism of human acquired immunodeficiency syndrome - Yan-Mei Huang; Xue-Zhi Hong; Jia-Hua Xu; Jiang-Xi Luo; Han-You Mo; Hai-Lu Zhao (Immunologic Research, 2016)

Minocycline Protects Against NLRP3 Inflammasome-Induced Inflammation and P53-Associated Apoptosis in Early Brain Injury After Subarachnoid Hemorrhage - Jianru Li; Jingsen Chen; Hangbo Mo; Jingyin Chen; Cong Qian; Feng Yan; Chi Gu; Qiang Hu; Lin Wang; Gao Chen (Molecular Neurobiology, 2016)

Identification of a Novel Rat NR2B Subunit Gene Promoter Region Variant and Its Association with Microwave-Induced Neuron Impairment - Li-Feng Wang; Da-Wei Tian; Hai-Juan Li; Ya-Bing Gao; Chang-Zhen Wang; Li Zhao; Hong-Yan Zuo; Ji Dong; Si-Mo Qiao; Yong Zou; Lu Xiong; Hong-Mei Zhou; et al. (Molecular Neurobiology, 2016)

Cotton S-adenosylmethionine decarboxylase-mediated spermine biosynthesis is required for salicylic acid- and leucine-correlated signaling in the defense response to Verticillium dahliae - Hui-Juan Mo; Yan-Xiang Sun; Xiao-Li Zhu; Xing-Fen Wang; Yan Zhang; Jun Yang; Gui-Jun Yan; Zhi-Ying Ma (Planta, 2016)

Sodium Para-aminosalicylic Acid Protected Primary Cultured Basal Ganglia Neurons of Rat from Manganese-Induced Oxidative Impairment and Changes of Amino Acid Neurotransmitters - Shao-Jun Li; Yong Li; Jing-Wen Chen; Zong-Xiang Yuan; Yu-Huan Mo; Guo-Dong Lu; Yue-Ming Jiang; Chao-Yan Ou; Fang Wang; Xiao-Wei Huang; Yi-Ni Luo; Shi-Yan Ou; et al. (Biological Trace Element Research, 2016)

A novel thermostable and organic solvent-tolerant lipase from Xanthomonas oryzae pv. oryzae YB103: screening, purification and characterization - Qiurun Mo; Aili Liu; Hailun Guo; Yan Zhang; Mu Li (Extremophiles, 2016)

Biodegradation of di-n-butylphthalate and phthalic acid by a novel Providencia sp. 2D and its stimulation in a compost-amended soil - Hai-Ming Zhao; Huan Du; Nai-Xian Feng; Lei Xiang; Yan-Wen Li; Hui Li; Quan-Ying Cai; Ce-Hui Mo (Biology and Fertility of Soils, 2016)

Influence of different formulations on chlorpyrifos behavior and risk assessment in bamboo forest of China - Yihua Liu; Runhong Mo; Fubin Tang; Yan Fu; Yirong Guo (Environmental Science and Pollution Research, 2015)

Cotton ACAULIS5 is involved in stem elongation and the plant defense response to Verticillium dahliae through thermospermine alteration - Huijuan Mo; Xingfen Wang; Yan Zhang; Jun Yang; Zhiying Ma (Plant Cell Reports, 2015)

Sequential dynamic artificial neural network modeling of a full-scale coking wastewater treatment plant with fluidized bed reactors - Hua-Se Ou; Chao-Hai Wei; Hai-Zhen Wu; Ce-Hui Mo; Bao-Yan He (Environmental Science and Pollution Research, 2015)

Linear regression model for predicting interactive mixture toxicity of pesticide and ionic liquid - Li-Tang Qin; Jie Wu; Ling-Yun Mo; Hong-Hu Zeng; Yan-Peng Liang (Environmental Science and Pollution Research, 2015)

Effects of the size and morphology of zinc oxide nanoparticles on the germination of Chinese cabbage seeds - Lei Xiang; Hai-Ming Zhao; Yan-Wen Li; Xian-Pei Huang; Xiao-Lian Wu; Teng Zhai; Yue Yuan; Quan-Ying Cai; Ce-Hui Mo (Environmental Science and Pollution Research, 2015)

Effect of the Shenfu Injection Combined with Early Goal-Directed Therapy on Organ Functions and Outcomes of Septic Shock Patients - Mao-qin Li; Cui-gai Pan; Xiao-meng Wang; Xun Mo; Zai-xiang Shi; Ji-yuan Xu; Yan-jun Xu; Guan-jie Han (Cell Biochemistry and Biophysics, 2015)

17β-Estradiol Ameliorates Light-Induced Retinal Damage in Sprague–Dawley Rats by Reducing Oxidative Stress - Shaolan Wang; Baoying Wang; Yan Feng; Mingshu Mo; Fangying Du; Hongbo Li; Xiaorui Yu (Journal of Molecular Neuroscience, 2015)

Spatial distribution of heavy metal contamination in soils near a primitive e-waste recycling site - Sheng-Xiang Quan; Bo Yan; Fan Yang; Ning Li; Xian-Ming Xiao; Jia-Mo Fu (Environmental Science and Pollution Research, 2015)

Functional relevance for multiple sclerosis-associated genetic variants - Xiang Lin; Fei-Yan Deng; Xing-Bo Mo; Long-Fei Wu; Shu-Feng Lei (Immunogenetics, 2015)

Correlations Between CT Perfusion Parameters and Vascular Endothelial Growth Factor Expression and Microvessel Density in Implanted VX2 Lung Tumors - Shoujia Ling; Dong Deng; Yan Mo; Xiaobo Zhang; Xuechun Guan; Qijun Wei (Cell Biochemistry and Biophysics, 2014)

Hemodiafiltration Combined with Resin-Mediated Absorption as a Therapy for Hyperlipidemic Acute Pancreatitis - Mao-qin Li; Zai-xiang Shi; Ji-yuan Xu; Bo Lu; Jia-qiong Li; Yan-jun Xu; Xiao-meng Wang; Song-mei Li; Xun Mo (Cell Biochemistry and Biophysics, 2014)

Large-scale screening maize germplasm for low-phosphorus tolerance using multiple selection criteria - Li-tian Zhang; Jia Li; Ting-zhao Rong; Shi-bin Gao; Feng-kai Wu; Jie Xu; Meng-lu Li; Mo-ju Cao; Jing Wang; Er-liang Hu; Ya-xi Liu; Yan-li Lu (Euphytica, 2014)

Expression of three essential antioxidants of Helicobacter pylori in clinical isolates - Yan-yan Shi; Mo Chen; Yue-xia Zhang; Jing Zhang; Shi-gang Ding (Journal of Zhejiang University-SCIENCE B, 2014)

Coffee consumption and prostate cancer risk: an updated meta-analysis - Yu Lu; Limin Zhai; Jie Zeng; Qiliu Peng; Jian Wang; Yan Deng; Li Xie; Cuiju Mo; Shi Yang; Shan Li; Xue Qin (Cancer Causes & Control, 2014)

Efficacy of Various Combined Blood Purification Techniques for Treating Patients with Non-viral Acute Liver Failure - Mao-qin Li; Jia-qiong Li; Zai-xiang Shi; Ji-yuan Xu; Zhou Zhang; Fei Lu; Lin Li; Yan-jun Xu; Xun Mo; Bo Lu; Xiao-meng Wang; Li-li Ma; et al. (Cell Biochemistry and Biophysics, 2014)

Soil water affects transpiration response to rainfall and vapor pressure deficit in poplar plantation - Lixin Chen; Zhiqiang Zhang; Tonggang Zha; Kangle Mo; Yan Zhang; Xianrui Fang (New Forests, 2014)

Expression of SOCSs in human prostate cancer and their association in prognosis - Jian-guo Zhu; Qi-shan Dai; Zhao-dong Han; Hui-chan He; Ru-jun Mo; Guo Chen; Yan-fei Chen; Yong-ding Wu; Sheng-bang Yang; Fu-neng Jiang; Wei-hong Chen; Zhao-lin Sun; et al. (Molecular and Cellular Biochemistry, 2013)

17β-Estradiol Impedes Bax-Involved Mitochondrial Apoptosis of Retinal Nerve Cells Induced by Oxidative Damage via the Phosphatidylinositol 3-Kinase/Akt Signal Pathway - Hongbo Li; Baoying Wang; Chunhui Zhu; Yan Feng; Shaolan Wang; Muhammad Shahzad; Chenghu Hu; Mingshu Mo; Fangying Du; Xiaorui Yu (Journal of Molecular Neuroscience, 2013)

Peroxisome Proliferator-Activated Receptor γ Ligands Retard Cultured Vascular Smooth Muscle Cells Calcification Induced by High Glucose - Ye-Bo Zhou; Jing Zhang; Ding-Qiong Peng; Jin-Rui Chang; Yan Cai; Yan-Rong Yu; Mo-Zhi Jia; Wei Wu; You-Fei Guan; Chao-Shu Tang; Yong-Fen Qi (Cell Biochemistry and Biophysics, 2013)

Association of interleukin-1 receptor-associated kinase (IRAK1) gene polymorphisms (rs3027898, rs1059702) with systemic lupus erythematosus in a Chinese Han population - Yu Zhai; Ke Xu; Rui-Xue Leng; Han Cen; Wei Wang; Yan Zhu; Mo Zhou; Chen-Chen Feng; Dong-Qing Ye (Inflammation Research, 2013)

Down-regulation of the ErbB3 binding protein 1 in human bladder cancer promotes tumor progression and cell proliferation - Hui-chan He; Xiao-hui Ling; Jian-guo Zhu; Xin Fu; Zhao-dong Han; Yu-xian Liang; Ye-han Deng; Zhuo-yuan Lin; Guo Chen; Yan-fei Chen; Ru-jun Mo; Wei-de Zhong (Molecular Biology Reports, 2013)

Heavy metal contamination of urban soils and dusts in Guangzhou, South China - Quan-Ying Cai; Ce-Hui Mo; Hai-Qin Li; Huixiong Lü; Qiao-Yun Zeng; Yan-Wen Li; Xiao-Lian Wu (Environmental Monitoring and Assessment, 2013)

Effect of C/N ratios on the performance of earthworm eco-filter for treatment of synthetics domestic sewage - Yong-Jun Zhao; Cheng Yan; Yin-Liang Li; Ji-Hua Li; Mo Yang; Er Nie; Zheng Zheng; Xing-Zhang Luo (Environmental Science and Pollution Research, 2012)

Occurrence of Nonylphenol and Nonylphenol Monoethoxylate in Soil and Vegetables from Vegetable Farms in the Pearl River Delta, South China - Quan-Ying Cai; Hui-Juan Huang; Huixiong Lü; Ce-Hui Mo; Jun Zhang; Qiao-Yun Zeng; Jun-Jian Tian; Yan-Wen Li; Xiao-Lian Wu (Archives of Environmental Contamination and Toxicology, 2012)

Combined Toxicity of the Mixtures of Phenol and Aniline Derivatives to Vibrio qinghaiensis sp.-Q67 - Ling-Yun Mo; Shu-Shen Liu; Yi-Nian Zhu; Hai-Ling Liu; Hong-Yan Liu; Zhong-Sheng Yi (Bulletin of Environmental Contamination and Toxicology, 2011)

Nocardiopsis yanglingensis sp. nov., a thermophilic strain isolated from a compost of button mushrooms - Xia Yan; Hua Yan; Zenan Liu; Xiaodong Liu; Haiping Mo; Liping Zhang (Antonie van Leeuwenhoek, 2011)

M. tuberculosis H37Rv Infection of Chinese Rhesus Macaques - Jing Zhang; Yan-Qing Ye; Yong Wang; Ping-Zheng Mo; Qiao-Yang Xian; Yan Rao; Rong Bao; Ming Dai; Jun-Yan Liu; Ming Guo; Xin Wang; Zhi-Xiang Huang; et al. (Journal of Neuroimmune Pharmacology, 2011)

Variabilities of Two Drechslerella dactyloides Isolates in Korea and High Predacity Against Bursaphelenchus xylophilus - Zhen Wang; Chun-Yan Wang; Li-Juan Gu; Bai-Shen Sun; Dong-Liang Zhang; Lei Liu; Mi-Ra Lee; Chun-Ling Wang; Zheng Li; Eun-Kyung Mo; Chang-Keun Sung (Current Microbiology, 2011)

13C abundance, water-soluble and microbial biomass carbon as potential indicators of soil organic carbon dynamics in subtropical forests at different successional stages and subject to different nitrogen loads - Hua-Jun Fang; Gui-Rui Yu; Shu-Lan Cheng; Jiang-Ming Mo; Jun-Hua Yan; Shenggong Li (Plant and Soil, 2009)

Cloning and characterization of class 1 and class 2 insulin-like growth factor-I mRNA in Songliao black pig - Shuqi Xiao; Shuang Li; Jiabao Zhang; Shumin Zhang; Lisheng Dai; Yonghua Bao; Ning Jiang; Yan Gao; Zhongli Zhao; Delin Mo; Yaosheng Chen; Zhihui Zhao (Molecular Biology Reports, 2009)

ZNF418, a novel human KRAB/C2H2 zinc finger protein, suppresses MAPK signaling pathway - Yongqing Li; Dan Yang; Yan Bai; Xiaoyang Mo; Wen Huang; Wuzhou Yuan; Zhaochu Yin; Yun Deng; Oleg Murashko; Yuequn Wang; Xiongwei Fan; Chuanbing Zhu; et al. (Molecular and Cellular Biochemistry, 2008)

Screen p53 mutations in hepatocellular carcinoma by FASAY: A novel splicing mutation - Xiao-mo Wu; Jing-geng Fu; Wang-zhong Ge; Jiang-yan Zhu; Jun-yong Wang; Wei Zhang; Wei Qian; Ke-ke Huo (Journal of Zhejiang University-SCIENCE B, 2007)

Litterfall Production Along Successional and Altitudinal Gradients of Subtropical Monsoon Evergreen Broadleaved Forests in Guangdong, China - Guoyi Zhou; Lili Guan; Xiaohua Wei; Deqiang Zhang; Qianmei Zhang; Junhua Yan; Dazhi Wen; Juxiu Liu; Shuguang Liu; Zhongliang Huang; Guohui Kong; Jiangming Mo; et al. (Plant Ecology, 2006)

Effect of vinasse irrigation on the activity of three enzymes and agronomic characters at seedling stage of sugarcane - Wang Yi-Ding; Mo Yun-Chuan; Wang Wei-Hao; Li Yang-Rui; Ye Yan-Ping (Sugar Tech, 2006)

Roots of pioneer trees in the lower sub-tropical area of Dinghushan, Guangdong, China - Yan-ru Hao; Shao-lin Peng; Jiang-ming Mo; Xin-wei Liu; Zhuo-quan Chen; Kai Zhou; Jin-rong Wu (Journal of Zhejiang University-SCIENCE B, 2006)

Isolation of Virus from a SARS Patient and Genome-wide Analysis of Genetic Mutations Related to Pathogenesis and Epidemiology from 47 SARS-CoV Isolates - Ying Zhu; Mo Liu; Weiguang Zhao; Jianlin Zhang; Xue Zhang; Ke Wang; Chunfang Gu; Kailang Wu; Yan Li; Congyi Zheng; Gengfu Xiao; Huimin Yan; et al. (Virus Genes, 2005)

An optimized gossypol high-performance liquid chromatography assay and its application in evaluation of different gland genotypes of cotton - Yingfan Cai; Hong Zhang; Yu Zeng; Jianchuan Mo; Jinku Bao; Chen Miao; Jie Bai; Fang Yan; Fang Chen (Journal of Biosciences, 2004)

Production of Linolenic Acid by Mortierella isabellina Grown on Octadecanol - Mo Xian; Yijian Kang; Jicang Yan; Junhong Liu; Yingli Bi; Kaiji Zhen (Current Microbiology, 2002)

Seasonal variations of riverine organic carbon contents in Makou and Hekou gauge stations of the Zhujiang River, China - Quan-zhou Gao; Cheng-de Shen; Yan-min Sun; Wei-xi Yi; Jia-mo Fu; Guo-ying Sheng (Chinese Geographical Science, 2000)